Multi-modal therapeutic approaches to inflammatory bowel disease: plant-derived compounds, nanoparticle drug delivery systems, and gene-based interventions - Arooj Komal; Doua Ilyas; Muhammad Usman Khan; Muhammad Khalil ur Rehman; Tayyaba Hassan; Hina Ayub; Nokhba Naqi; Noor Ullah; Umair Ilyas (Molecular Biology Reports, 2026)

Structural dynamics and stability analysis of a novel ARSK variant confirms its role in MPS type X pathogenesis - Muhammad Bilal; Muhammad Fakhar; Thamir Eid; Nawal Helmi; Misbahuddin Rafeeq; Mehreen Gul; Hammal Khan; Muhammad Umair (Glycoconjugate Journal, 2026)

Geophysical and remote sensing insights into tectonics and mineralization of Hattian, Azad Jammu and Kashmir - Shahid Ahmed; Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Khawaja Umair Majeed; Junaid Yousif (Journal of Applied Geophysics, 2026)

Integrated sedimentological and petrographic constraints on early Himalayan foreland basin evolution, Sulaiman ranges, Pakistan - Muhammad Jehangir Khan; Shahid Ghazi; Xiaodong Yang; Syed Ahsan Hussain Gardezi; Mubashir Mehmood; Muhammad Aleem Zahid; Umair Khan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

From cratonic interiors to deltaic shores: Tectonic and paleoclimatic influences on the diagenetic evolution of Khewra Sandstone, Salt Range, Pakistan - Muhammad Ajaz Abbasi; Imran Khan; Atif Iqbal Abbasi; Muhammad Jamil; Nawaz Ikram; Syed Ahsan Hussain Gardezi; Zulfiqar Haider Awan; Umair Aftab Choudary; Abdul Wali Khan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Impacts of organic fertilization on Comammox abundance, ammonia oxidation rates and its relative contribution to N2O emissions in agricultural soils - Siyi Li; Muhammad Umair Hassan; Teng Yu; Chengyi Lao; Ziwei Wan; Lorenzo Barbanti; Muhammad Farooq; Huifang Xu (Pedobiologia, 2026)

Solar radio flux F10.7 forecasting via deep learning: A hybrid approach with LSTM and GRU - Mohsin Ghaffar Ghouri; Muhammad Umair; Manzoor Ahmed Hashmani (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

A review on sustainable aviation fuel production via diverse biomass and waste-derived feedstocks and cutting-edge conversion technologies - Wajahat Waheed Kazmi; Muhammad Wasi Syed; Muhammad Waqas; Umair Hassan Bhatti; Ahmed Omer; Mansoor Ali; Zulqarnain; Ishaq Kariim; Amjad Hussain; Faysal M. Al-Khulaifi (Biomass and Bioenergy, 2026)

Elevated DNA 5-hydroxymethylation promotes chondrocyte differentiation via TET-mediated epigenetic downregulation of hTERT in human mesenchymal stem cells - Naeem Ullah; Fazal Jalil; Muhammad Jaseem Khan; Muhammad Umair; Waseem Iqbal; Aamir Ali Khan (Histochemistry and Cell Biology, 2026)

Charcoal in the clouds: Holocene biomass burning records from the himalayas and economic implications for South Asian atmospheric systems - Hongyang Zhao; Linqi Du; Muhammad Umair (Anthropocene, 2026)

Retraction notice to “Minor mining, major influence: Economic implications and policy challenges of artisanal gold mining” [Resources Policy 91 (2024) 104886] - Miaozhi Yu; Yifan Wang; Muhammad Umair (Resources Policy, 2026)

Chronic ischemic heart disease and co-recorded depression on death certificates: national mortality trends in the United States - Sarim Hassan Shahab; Muhammad Uzair Afzal; Kanza Zainab; Esha Umair; Hadia Ghazala Masood; Umer Abdur Rahman (Next Research, 2026)

Micron-engineered biochar mitigates antimony and microplastics toxicity by reshaping soil microbiome and plant transcriptomic responses - Muhammad Umair Hassan; Waqar Ahmed; Lorenzo Barbanti; Huo Yuxin; Zhang Shujian; Faizah Amer Altihani; Su Qitao; Huang Guoqin (Journal of Hazardous Materials, 2026)

Bifunctional TiO2 (anatase, brookite, rutile)-based photocatalysis for environment remediation: Efficient simultaneous glyphosate degradation and H2 production - Muhammad Umair; Leonardo Palmisano; Hebah S. Jarusheh; Marianna Bellardita (Journal of Environmental Chemical Engineering, 2026)

Chitosan-crosslinked microwave-engineered biochar alleviates lead stress in Brassica napus by improving soil functioning and plant performance in Pb-contaminated soil - Fakhir Hannan; Yiwa Hu; Ahsan Ayyaz; Muhammad Iqbal; Muhammad Umair Yasin; Iram Batool; Juanjuan Li; Faisal Islam; Yasir Hamid; Muhammad Ahsan Farooq; Weijun Zhou (Journal of Environmental Management, 2026)

Transforming Banana Peel Waste into a Nano Biostimulant: Effects on Maize Seed Germination and Physio-Morphological Traits - Palwasha Sajjad; Umair Riaz; Azer Ahmadov; Tanveer-ul-Haq; Nazar Fareid; Faiza Hassan; Muhammad Adeel; Ayta Umar; Ren Maozhi; Muhammad Usman Aslam; Lamy Hamed (Journal of Plant Growth Regulation, 2026)

Jasmonic Acid and Abiotic Stress Tolerance: From Metabolic Flux to Hormone-Network Decision Making - Nazma Khan; Burhan Khalid; Muhammad Atiq Ashraf; Umair Khan; Rizwan Maqbool (Journal of Plant Growth Regulation, 2026)

Lactobacilli Mitigate Gut Inflammation by Modulating T-Helper/T-Regulatory Cells and Suppressing Signaling Pathways in Food-Derived Models - Md. F. Kulyar; Syed Umair Ali Shah Naqvi; Eiva Bernotiene; Muhammad Akhtar (Probiotics and Antimicrobial Proteins, 2026)
Intestinal inflammation disrupts epithelial integrity, fuels antibiotic resistance, and underlies disorders such as inflammatory bowel disease. Lactobacillus species, established inhabitants of traditional and contemporary fermented foods, are increasingly viewed as bioactive cultures that shape host immunity and support formulation of next-generation functional foods. This review integrates multidisciplinary evidence from in vitro studies, animal models, human observations, and multi omics datasets to clarify how dietary or probiotic Lactobacillus strains alleviate gut inflammation. Particular attention is given to strain specific effects on T-helper/T-regulatory cell balance, suppression of TLR4-MyD88, NF-κB, MAPK, and NLRP3 signaling cascades, and the influence of food matrices, microencapsulation, dosage, and processing parameters on bacterial viability and efficacy, which are the factors central to food industry application. Across models, Lactobacillus consistently down regulates pro-inflammatory Th1/Th17 responses, while expanding forkhead box protein 3 (Foxp3⁺) T reg, leading to reduced TNF-α, IL-1β, and IL-6 and elevated IL-10 and TGF-β. Short chain fatty acids (SCFAs) and indole metabolites derived from fermentation further dampen NF-κB activity and reinforce epithelial barrier function. Food matrix studies show that dairy and cereal formulations enhance probiotic survival, whereas acidic beverages often require micro encapsulation; a daily intake of ~ 10 10 CFU appears both effective and safe. Taken together, these insights position Lactobacillus as a scientifically robust, industry ready tool for developing anti-inflammatory foods, prioritizing future work for well-designed human feeding trials that couple multi-omics read outs and optimizing strain matrix combinations.

Robust interfacial network and ionic conduction of carbon-doped hexagonal boron nitride for dual-mode strain and humidity sensor - Muhammad Mujtaba Syed; Balamurugan Thirumalraj; Abdallah Kamal; Baosong Li; Dezhuang Ji; Dawei Zhang; Muhammad Umair Khan; Baker Mohammad; Kin Liao; Lianxi Zheng (Chemical Engineering Journal, 2026)

Impact of insect pollinators on the yield and quality of cucumber (Cucumis sativus L.) - Muhammad Mamoon-ur-Rashid; Farheen Sayyam; Habib Ali; Modhi O. Alotaibi; Ammara Riaz; Xu Danping; Muhammad Umair Sardar; Aftab Ahmad; Zhuo Zhihang (International Journal of Tropical Insect Science, 2026)

GCMS, phytochemical analysis, biological potential of dichloromethane extract of Yucca elephantipes regel roots: in vitro and in silico studies - Muhammad Shoaib Khan; Mehreen Jabeen; Farhan Siddique; Sajjad Ahmad; Amna Aqdas; Umair Jillani; Yasir Zaman; Abdulrahman Alshammari; Norah A. Albekairi (Natural Product Research, 2026)

Advances in Coated Urea Technology: Toward Climate-responsive, Microbiome-friendly, and Site-specific Nitrogen Management - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Shazia Hanif; Aqsa Andleeb Sial; Muhammad Umair Hassan; Tahani A.Y. Asseri; Rehab O. Elnour (Journal of Soil Science and Plant Nutrition, 2026)

Geochemical and petrographic insights into the Lumshiwal Formation (NW Himalayas): implications for provenance, paleoclimate, and economic potential - Syed Nohman Gilani; Muhammad Saleem Mughal; Khawaja Umair Majeed; Hammad Tariq Janjuhah; Yongzhi Wang; Muhammad Atif Bilal; Ahmer Bilal; Syed Wajee-Ul Hassan Gillani; Muhammad Hafeez (Carbonates and Evaporites, 2026)

Retraction Note: Assessment of genetic diversity in cotton genotypes using simple sequence repeat (SSR) markers: insights from interspecific and intraspecific variations - Muhammad Arslan; Akash Fatima; Fatima Javeria; Sehrish Ijaz; Umair Riaz; Gulnaz Saleem; Mounir M. Bekhit; Milad A. Mezher; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

pH-responsive pea protein-sodium alginate hydrogel beads for freshness monitoring in protein drinks: Structural and molecular insight - Khubaib Ali; Nadia Niaz; Fedrick C. Mgomi; Faizan Ul Haq; Waqas Ashraf; Muhammad Umair Khalid; Qingling Wang; Mangang Wu (Food Hydrocolloids, 2026)

Brassinosteroids: Key Players to Improve Drought Tolerance and Crop Productivity - Muhammad Inzamam-UL-Haq; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Sezai Ercişli; Uthman Balgith Algopishi; Fatima M. Abbas; Mohamed Hashem; Muhammad Mahmood Iqbal; Muhammad Umair Hassan (International Journal of Plant Production, 2026)

Sulfur-Coated Urea Improves Rice productivity, Nitrogen Use Efficiency, and Soil Nitrogen Dynamics Under Alternate Wetting and Drying System - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Muhammad Bilal Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Umair Hassan; Uthman Balgith Algopishi; Mohamed Hashem; Sezai Ercişli (International Journal of Plant Production, 2026)

Data augmentation and normalization strategies for improving satellite image segmentation - Ayesha Saadia; Muhammad Ishfaq; Muhammad Umair; Iqbal Murtza; Munahil Yaqoob (Earth Science Informatics, 2026)

Influence of functional diversity on aboveground biomass accumulation in subtropical sub montane forests - Muhammad Majeed; Akash Jamil; Yongheng Gao; Ghulam Yasin; Umair Younas; Elena Pismennaya; Ksenia Myachina; Nasir Qadir (Journal of Mountain Science, 2026)

Genomic surveillance of Influenza, SARS-CoV-2, and RSV in patients from Islamabad and Rawalpindi, Pakistan: a 2023-24 perspective - Zunera Jamal; Syed Adnan Haider; Fahad Humayun; Qasim Ali; Rabia Hakim; Muhammad Salman; Massab Umair (Archives of Virology, 2026)

Brain Delivery of a Kv1.3-Blocking Peptide is not Enhanced by Conjugation to Blood–Brain Barrier Shuttle Peptides - Dorothy C. C. Wai; Liam M. Koehn; Ethan Kreutzer; Pranav Runwal; Muhammad Umair Naseem; Gyorgy Panyi; David I. Finkelstein; Joseph A. Nicolazzo; Raymond S. Norton (International Journal of Peptide Research and Therapeutics, 2026)
Purpose The voltage-gated potassium channel K V 1.3 is upregulated on pro-inflammatory microglia, and its blockade is effective in reducing neuroinflammation in vitro and in vivo. The most potent and selective K V 1.3 blockers identified to date are disulfide-rich, venom-derived peptides, which are largely excluded from the brain by the blood–brain barrier (BBB). As BBB shuttle peptides have been reported to promote receptor-mediated transport of macromolecules and nanoparticles across the BBB, we have conjugated two such shuttle peptides, MTfpep (MTf) and Angiopep-2 (Ang2), to HsTX1[R14A], a K V 1.3-blocking peptide with 34 residues and four disulfide bonds, using click chemistry. Results NMR spectroscopy showed that the conjugates adopted the same fold as HsTX1[R14A], and electrophysiology assays demonstrated the retention of nanomolar K V 1.3 inhibition. Liquid chromatography tandem mass spectrometry (LC-MS/MS) assays were developed to quantify HsTX1[R14A] and MTf-HsTX1[R14A] in buffer, mouse plasma and brain homogenate; however, sufficient analytical sensitivity could not be achieved for Ang2-HsTX1[R14A]. Assessment of peptide permeability in in vitro BBB models showed no evidence of enhanced permeability of MTf-HsTX1[R14A] relative to HsTX1[R14A]. Following intravenous administration of MTf-HsTX1[R14A] to C57BL/6 mice at 4 mg/kg, plasma concentrations were detectable up to 120 min post-dose, but brain concentrations of MTf-HsTX1[R14A] remained below the limit of detection at all timepoints measured. Conclusion Our results imply that the BBB shuttle peptide MTfpep failed to facilitate brain entry of this cargo. Nevertheless, the click chemistry methods developed for HsTX1[R14A] will facilitate its modular assembly with other brain-targeting ligands and are applicable to conjugation of other disulfide-rich peptides.

Interface synergistic-driven electronic modulation in amorphous CoFeB@g-C3N4 for high-performance bifunctional OER/HER electrocatalysis - Abdul Haq; Anuj Kumar; Muhammad Arif; Umair Azhar; Huma Ahmad; Unaiza Talib; Mahnoor Ahmed; Muhammad Asim Mushtaq; Muhammad Sagir; Muhammad Faheem Maqsood; Kumar Venkatesan; Ghulam Yasin (Journal of Environmental Chemical Engineering, 2026)

Phytochemical Profiling and Evaluation of the Anti-inflammatory and Antinociceptive Effects of Lilium polyphyllum Bulb Using In Silico, In Vitro and In Vivo Models - Haider Ali; Shafiq Ur Rahman; Umair Sayad; Atif Ali Khan Khalil; Muzaffar Abbas; Muhammad Shahid (Journal of Pharmaceutical Innovation, 2026)

A Novel Homozygous Loss-of-Function Variant in GPR156 Delineates Non-syndromic Hearing Loss - M. Muaaz Aslam; Safdar Abbas; Shoaib Nawaz; Gohar Zaman; Ishtiaq Ahmed; Misbahuddin Rafeeq; Ziaullah M. Sain; Alaa Hamed Habib; Muhammad Umair; Khadim Shah (Biochemical Genetics, 2026)

Synergistic efficacy of Azadirachta indica and biocontrol agents in mitigating Meloidogyne javanica infection in peach - Muhammad Saeed; Tariq Mukhtar; Raees Ahmed; Umair Mehmood; Muhammad Aamir Iqbal (Australasian Plant Pathology, 2026)

Biochar Amendment Improved Growth and Yield of Fragrant Rice and Reduced Arsenic (As) Accumulation under As-contaminated Irrigation Water - Umair Ashraf; Talat Mansha; Shakeel Ahmad Anjum; James DeDecker; Abrar Hussain; Fahd Rasul; Muhmmad Abrar; Muhammad Ishfaq (Water, Air, & Soil Pollution, 2025)

Predicting rice yield and impact of climate change on rice production using machine learning models - Khawaja T. Tasneem; Muhammad Umair Shahzad; Javed Rashid; Kamal M. Othman; Tania Zafar; Muhammad Faheem (Theoretical and Applied Climatology, 2025)
Climate change poses a critical threat to agricultural sustainability, with direct implications for the global food supply. Rice, a staple crop throughout Asia, is particularly vulnerable to variations in temperature and rainfall, making it essential to understand how it responds to changing climatic conditions. This study integrates historical climate records, rice yield data, and projections from Global Climate Models (GCMs; CMIP3) to assess the potential effects of climate change on rice production in Punjab, Pakistan. We employed multiple machine learning approaches, including Multiple Linear Regression (MLR), Boosted Tree Regression (BTR), Probabilistic Neural Network (PNN), Generalized Feed-Forward (GFF) Neural Network, Linear Regression (LR), and a Multilayer Perceptron (MLP) Artificial Neural Network. The models were trained and validated using observed climate and yield data from 1990 to 2020. Future yields were projected under three IPCC emission scenarios (SR-A2, SR-A1B, SR-B1) through the year 2050. Model evaluation showed that the Multilayer Perceptron (MLP) achieved the highest predictive performance ( $$R^2$$ = 0.791, R = 0.868, MAE = 0.215, MSE = 0.0869, NMSE = 0.3681), followed by Boosted Tree Regression (BTR; $$R^2$$ = 0.779, R = 0.845, MAE = 0.334, MSE = 0.1308). The Probabilistic Neural Network (PNN) and Generalized Feed-Forward (GFF) model also performed respectably ( $$R^2$$ = 0.745, R = 0.811, MAE = 0.176, MSE = 0.380 and $$R^2$$ = 0.643, R = 0.825, MAE = 0.398, MSE = 0.178, respectively). In contrast, Multiple Linear Regression (MLR) and Linear Regression (LR) performed poorly, with low $$R^2$$ values (0.535), underscoring their inability to capture the non-linear relationships between climate variables and yield. Our analysis identifies maximum temperature as the primary climatic driver of yield loss. Based on the projections, we estimate an average yield decline of 0.12% by 2050. This study demonstrates that non-linear machine learning models, particularly the MLP, are essential for reliable agricultural forecasting under climate change. The results highlight the growing vulnerability of rice production to rising temperatures and provide a robust evidence base for designing adaptation strategies, such as developing heat-tolerant rice varieties, to enhance food security in vulnerable regions.

Correction: Advanced modeling and visualizations of the Chafee–Infante equation in reaction–diffusion systems - Saman Naz; Umair Asghar; Muhammad Imran Asjad; M. S. Alqarni (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Advanced modeling and visualizations of the Chafee–Infante equation in reaction–diffusion systems - Saman Naz; Umair Asghar; Muhammad Imran Asjad; M. S. Alqarni (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Biochar and Sheep Manure with Reduced Nitrogen Application Increases Rice Productivity and Mitigates N2O Emissions in Paddy Fields - Tahir Abbas Khan; Huang Guoqin; Muhammad Umair Hassan; Mehmood Ali Noor; Muhammad Aamer; Tahani A.Y. Asseri; Rehab O. Elnour (Journal of Soil Science and Plant Nutrition, 2025)

An effective encryption approach using a combination of a non-chain ring and a four-dimensional chaotic map - Muhammad Umair Safdar; Tariq Shah; Asif Ali (Cognitive Neurodynamics, 2025)

Sedimentology and biostratigraphy of the Cretaceous–Paleocene successions in Northern Pakistan: evidence from the Hazara, Kala Chitta, Potwar, and Kohat Basins - Syed Kamran Ali; Hafiz Sohaib Bashir; Asim Qadir; Muhammad Saleem Mughal; Khurram Iqbal; Abrar Niaz; Khawaja Umair Majeed (Carbonates and Evaporites, 2025)

Dietary levan as a feed additive: Effects on growth performance, meat quality, immune response, and gut health in broiler chickens - Damian Konkol; Marta Kuźmińska-Bajor; Jan P. Madej; Ewa Popiela; Magdalena Lis; Maciej Kuczkowski; Marianna Szczypka; Kamil Sierżant; Muhammad Umair Ashgar; Katarzyna Leicht; Małgorzata Korzeniowska; Cassandra Ceccopieri; et al. (Animal Feed Science and Technology, 2025)

Environmental extremes in cholistan rangeland ecosystem: effects on floral diversity, rangeland productivity, and carrying capacity - Muhammad Abid; Muhammad Rafay; Muneeb Khalid; Muhammad Umair Riaz (Brazilian Journal of Botany, 2025)

Interfacial engineering of CdMnS/gC3N4@rGO heterostructure for visible light-driven photocatalytic degradation of ciprofloxacin - Umair Alam; Qamar T. Siddiqui; Rishabh A. Omar; Mohammad Kashif; Zahid M. Bhat; Muhammad A.Z.G. Sial; Jae-Jin Shim; Mohammad Qamar; Nishith Verma (Journal of Water Process Engineering, 2025)

Influence of cationic, anionic, and non-ionic surfactants on in-situ growth of polyaniline on alumina ceramic membranes for the effective crude oil-in-water emulsion separation: Experimental and machine learning approaches - Muhammad Saad Khan; Umair Baig; Abdul Waheed; Sohaib Abdelazem; Isam H. Aljundi (Desalination, 2025)

Effect of the freezer and straw positioning on the post-thaw quality of bull spermatozoa: A comparative study - Marie Luis Neubert; Muhammad Umair Khan; Markus Jung; Árpád Csaba Bajcsy; Martin Schulze (Animal Reproduction Science, 2025)

Retraction notice to “Synergistic effect of silicon and arbuscular mycorrhizal fungi reduces cadmium accumulation by regulating hormonal transduction and lignin accumulation in maize” [Chemosphere 346, January 2024, 140507] - ShahRukh Khan; Zubair Ahmad; Zeeshan Khan; Umair Khan; Muhammad Asad; Tariq Shah (Chemosphere, 2025)

Quantitative Analysis of Pesticide Residues in Guava (Psidium guajava L.) Fruit by Using High Performance Liquid Chromatography - Rashad Qadri; Abdul Haseeb Ahmed; Muhammad Umair Ashraf; Muhammad Tahir Akram; Khalid Hussain; Muhammad Azam; Muhammad Imran Khan; Muhammad Mumtaz Khan (Applied Fruit Science, 2025)

Varietal and Geographic Influences on Fruit Quality Traits of Pomegranate (Punica granatum L.) - Muhammad Umair; Ishtiaq Ahmad Rajwana; Kashif Razzaq; Sami Ullah; Umair Riaz; Rashid Iqbal; Saltanat Aghayeva; Maximilian Lackner (Applied Fruit Science, 2025)

Integrated study of the deformed phosphorite dolomite of the Early Cambrian Sirban formation in the Lesser Himalayas, Pakistan - Khawaja Umair Majeed; Muhammad Saleem Mughal; Xijuan Tan; Sara Criniti; Massimo Civitelli; Muhammad Rustam Khan; Shoukat Hussain Khan; Salvatore Critelli (Acta Geochimica, 2025)

Retraction notice to “Template-based textural modifications of polymeric graphitic carbon nitrides towards waste water treatment” [Chemosphere 302, September 2022,134792] - Umair Azhar; Muhammad Sohail Bashir; Muhammad Babar; Muhammad Arif; Afaq Hassan; Asim Riaz; Rana Mujahid; Muhammad Sagir; Saadat Ullah Khan Suri; Pau Loke Show; Jo-Shu Chang; Kuan Shiong Khoo; et al. (Chemosphere, 2025)

Retraction notice to “Comparative study of ozonation and ozonation catalyzed by Fe-loaded biochar as catalyst to remove methylene blue from aqueous solution” [Chemosphere 307 Part 1, November 2022, 135738] - Muhammad Babar; Hafiz Muhammad Shahzad Munir; Aamna Nawaz; Naveed Ramzan; Umair Azhar; Muhammad Sagir; Muhammad Suleman Tahir; Amir Ikhlaq; Siti Nuurul huda Mohammad Azmin; Muhammad Mubashir; Kuan Shiong Khoo; Kit Wayne Chew (Chemosphere, 2025)

Nano-engineered biochar enhances soil microbial interactions and maize transcriptomic pathways for cadmium detoxification - Muhammad Umair Yasin; Sajid Muhammad; Nana Chen; Fakhir Hannan; Muhammad Afzal; Zulqarnain Haider; Bahar Ali; Irshan Ahmad; Muhammad Rehman; Yinbo Gan (Journal of Hazardous Materials, 2025)

Hydrogen bond-mediated reversible BHT/PVA nanocarriers integrating sustained release kinetics and small-size synergy for potentiated pesticide stability and longevity - Hongfa Duan; Xiaochi Liu; Lulu Bian; Zhongyi Li; Ning Li; Muhammad Umair Sial; Zhe Sun; Haiqiang Gao; Beixing Li; Daxia Zhang; Feng Liu (Chemical Engineering Journal, 2025)

Global decline of aquatic and terrestrial insects driven by climate change and anthropogenic impacts: The interaction of multiple stressors and disruption of niche conservatism - Muhammad Farooq; Umair Khan; Muhammad Adnan; Waqar Younas; Nimra Bashir Qureshi; Qazi Muhammad Yasir; Qinghua Cai; Ming-Chih Chiu (Biological Conservation, 2025)

Microbial Synthesis of ZnO Nanoparticles: A Green Strategy for Mitigating Wastewater Stress in Wheat (Triticum aestivum) - Aneeza Ishfaq; Irfan Haidri; Usman Shafqat; Imran Khan; Hafiz Muhammad Rizwan; Muhammed Umair Hassan; Muhammad Irfan; Muhammad Adnan; Faisal Mahmood (Water, Air, & Soil Pollution, 2025)

Utilizing genetic resources to develop yellow rust-resistant and high-yielding wheat genotypes across diverse environments - Hassan Mujtaba; Fahim Ullah Khan; Muhammad Sufyan; Israr Ud Din; Manzoor Ahmad; Asad Shah; Umair Bin Qasim (Genetic Resources and Crop Evolution, 2025)

The use of phytobiotics in the form of complexed organometallic phytoncides and micronized herbs in the nutrition of Ross 308 broiler chickens: Effects on growth performance, meat quality, and immune response - Marcin Gumowski; Cassandra Ceccopieri; Jan P. Madej; Katarzyna Leicht; Małgorzata Korzeniowska; Anna Lipińska; Kamil Sierżant; Damian Konkol; Henryk Różański; Muhammad Umair Asghar; Mariusz Korczyński (Animal Feed Science and Technology, 2025)

Driving innovation in fast-food industry: integrating green HRM, green empowerment, and green CSR - Jamshed Khalid; Mi Chuanmin; Muhammad Umair Ashraf; Muhammad Haroon Rasheed; Muhammad Shahid Rasheed (Environment, Development and Sustainability, 2025)

RNA modification: A contemporary review of pseudouridine (Ψ) and its role in functional plant biology - Ahsan Khan; Gatera Anicet; Hafiz Umair Asdullah; Muhammad Ahmad Hassan; Youhong Song (Plant Science, 2025)

Quantifying pluvial flood simulation in ungauged urban area; A case study of 2022 unprecedented pluvial flood in Karachi, Pakistan - Umair Rasool; Xinan Yin; Zongxue Xu; Muhammad Awais Rasool; Mureed Hussain; Jamil Siddique; Nguyen Thanh Hai (Journal of Hydrology, 2025)

Stage-dependent synergistic impacts of AM fungi and rhizobacteria on phytohormone mediation and field productivity in dryland maize - Muhammad Abrar; Ying Zhu; Wen-Shan Li; Muhammad Aqeel; Umair Ashraf; Muhammad Maqsood Ur Rehman; Jian-Ming Li; Xiao-Fang Gong; Wasim Khan; Wei Wang; You-Cai Xiong (Field Crops Research, 2025)

Multidimensional geophysical insights into hydrocarbon prospectivity in structurally complex fold-and-thrust belt system - Muhammad Idrees; Umair Khan; Shafqat Hussain; Zhongsheng Li (Journal of Earth System Science, 2025)

Rosmarinic acid attenuates photophobia, hyperalgesia and neuroinflammation during nitroglycerine induced migraine like headache in mice - Maira Anwar; Ismail Badshah; Babar Murtaza; Syed Muzzammil Masaud; Umair Ilyas; Amber Kiyani; Danish Patoli; Muhammad Tariq Khan (Natural Product Research, 2025)

Efficacy of sustainable Nano Fillers on the viscoelastic behavior and energy absorption of 3D woven green composites - Muhammad Arslan Khalid; Tehseen Ullah; Khubab Shaker; Muzzamal Hussain; Muhammad Ayub Asghar; Muhammad Umair (Environment, Development and Sustainability, 2025)

The extractive industries transparency initiative: Achieving disclosure, but falling short on corruption reduction - Yuanguo Li; Muhammad Umair; Shafa Guliyeva; Zibeyda Shakaraliyeva (The Extractive Industries and Society, 2025)

The Critical Role of Jasmonic Acid to Induce Salt Tolerance and Improve Crop Productivity: Review and Prospective - Tahir Abbas Khan; Huang Guoqin; Hamad Khan; Haocheng Wang; Mohammed Obeid Alshaharni; Gamal Awad El-Shaboury; Sameer H. Qari; Muhammad Umair Hassan (Journal of Soil Science and Plant Nutrition, 2025)

Mitigating the Greenhouse Gases Intensity and Improving Fine Rice Productivity with Coated Urea Fertilizers in Semi-Arid Conditions - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Hafiz Abdul Wahab; Faisal Nadeem; Rikza Awan; Uthman Balgith Algopishi; Mohamed Hashem; Muhammad Umair Hassan (Journal of Soil Science and Plant Nutrition, 2025)

Fodder Quality, Morphological and Biochemical Characteristics of Mombasa Grass (Megathyrsus maximus) Under Differently Primed Seeds - Muhammad Abdullah Saleem; Asif Iqbal; Umair Gull; Muhammad Iqbal (Journal of Crop Health, 2025)

Assessing the impact of air pollution on global and diffuse solar radiation in Karachi, Pakistan: a comparative analysis of multiple linear regression and artificial neural network models - Muhammad Uzair Yousuf; Abid Ali; Muhammad Umair (Theoretical and Applied Climatology, 2025)

Life cycle assessment of lignite-fueled ultra-supercritical coal-fired power plant with evaluation of solar energy integration - Muhammad Uzair Yousuf; Mubashir Ali Siddiqui; Munesh Kumar; Muhammad Umair (Fuel, 2025)

Evaluation of antibody titer and associated risk factors of goat pox vaccine against lumpy skin disease in crossbred buffaloes - Adili Abulaiti; Zahid Naseer; Zulfiqar Ahmed; Shijun Tian; Wenju Liu; Muhammad Shoaib; Asghar Khan; Mohamed Abdelrahman; Faisal Ayub Kiani; Abid Hussain; Aftab Shaukat; Umair Riaz; et al. (Veterinary Research Communications, 2025)

Flood characteristics and risk analysis in small watersheds on the Loess Plateau under extreme heavy rainfall - Muhammad Imran; Jingming Hou; Tian Wang; Qingshi Zhou; Donglai Li; Majid Habib Khan; Irfan Ullah; Rana Shahzad Noor; Muhammad Umair; Shakeel Hussain (Natural Hazards, 2025)

Immunomodulatory properties of a methanolic extract of Ficus lyrata mitigate inflammation in Complete Freund’s Adjuvant-induced arthritis - Anam Iftikhar; Mohammad Saleem; Syed Atif Raza; Adrian Achuthan; Rodney Luwor; Taha Muhammad; Umair Majeed (Inflammopharmacology, 2025)

Seismic safety assessment of buildings and perceptions of earthquake risk among communities in Mingora, Swat, Pakistan - Muhammad Umair Raza; Faheem Butt; Farhan Ahmad; Rana Muhammad Waqas (Innovative Infrastructure Solutions, 2025)
Pakistan has experienced several devastating earthquakes, including the 2005 Kashmir earthquake, which resulted in significant loss of life and damage. Mingora City, located in Seismic Zone 3, is particularly vulnerable and requires seismic evaluations and retrofitting of buildings to prevent future casualties and building collapses. Due to the high costs and complexity of seismic assessments, it is impractical to assess all buildings. This study used the FEMA P-154 Rapid Visual Screening (RVS) method to assess 210 buildings. The study also examined local residents’ risk perceptions through interviews. Findings revealed that most buildings had plan and vertical irregularities, such as short columns or soft storeys, and over 90% of buildings fall within damage grades 4 and 5, highlighting the urgent need for retrofitting. Poor construction quality and lack of maintenance were also noted, with 37% of buildings showing damage. Public awareness of earthquake safety was low, and 89.5% of residents agreed on the need for better education. The study highlights the need for public awareness campaigns on earthquake risks and safety.

A novel CLRN2 variant: expanding the mutation spectrum and its critical role in isolated hearing impairment - Farooq Ahmad; Arif Mahmood; Ibrahim Abdullah Almazni; Afnan Mohammed Shakoori; Fatemah Alhakami; Qamre Alam; Muhammad Ismail; Muhammad Umair (Genes & Genomics, 2025)

Advancements in metal selenide nanocomposites for efficient photocatalytic water splitting applications - Zeshan Ali Sandhu; Soha Ghaffar; Muhammad Asam Raza; Noor ul Huda; Sufyan Ashraf; Umair Talat; Areej Chauhdary; Hamza Gulzarab; Abdullah G. Al-Sehemi (Fuel, 2025)

Comparative efficacy of chitosan-HPMC-based nanoencapsulation and ultrasonic treatment of thymol-cinnamaldehyde for controlling Rhizopus stolonifer in papaya: In vitro and in vivo studies - Hsu Mon Phyo; Qais Ali Al-Maqtari; Norzila Othman; Yulun Chen; Muhammad Umair Khalid; Mudassar Hussain; Weirong Yao (Food Research International, 2025)

RETRACTED ARTICLE: Assessment of genetic diversity in cotton genotypes using simple sequence repeat (SSR) markers: insights from interspecific and intraspecific variations - Muhammad Arslan; Akash Fatima; Fatima Javeria; Sehrish Ijaz; Umair Riaz; Gulnaz Saleem; Mounir M. Bekhit; Milad A. Mezher; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Physicochemical profiling and health risk evaluation of effluents from textile industries: insights from Faisalabad, Pakistan - Hina Sattar; Muhammad Anwar-ul-Haq; Humera Aziz; Umair Riaz; Ahmad Mahmood; Muhammad Rizwan; Munaza Naseem; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Toxicology and Environmental Health Sciences, 2025)

Multiferroic Y Sn co-doped BiFeO3 2D nanoplates for enhanced photocatalytic degradation of cationic dyes: Synthesis, chemistry and mechanisms - Ahmad Umair; Mirza Mahmood Baig; Sheraz Yousaf; Muhammad Touqeer; Mehboob Hassan; Ali Ahmad; Joon Kim; Hyuntae Ju; Seung Goo Lee (Journal of Water Process Engineering, 2025)

Tailoring the electrochemical performance of rods-like Co-MOF: Fe-derived Co3O4: Fe electrodes for supercapacitor applications - Maryam Shah; Sonadia; Zoya Iqbal; Anwar Ul-Hamid; Muhammad Umair Mushtaq; Fahad Azad (Fuel, 2025)

Xylooligosaccharides: A comprehensive review of production, purification, characterization, and quantification - Khubaib Ali; Nadia Niaz; Muhammad Waseem; Waqas Ashraf; Mudassar Hussain; Muhammad Umair Khalid; Assam Bin Tahir; Ali Raza; Imran Mahmood Khan (Food Research International, 2025)

Simultaneous alleviation of antimony toxicity in rice and in-Vitro bio-accessibility by using biochar and seaweed based fertilizer blend - Muhammad Umair Hassan; Huang Guoqin; Muhammad Nawaz; Adnan Noor Shah; Shujuan Li; Tahir Abbas Khan; Khalid Mashay Al-Anazi; Mehmood Ali Noor; Adnan Rasheed; Xu Huifang; Sezai Ercisli (Environmental Pollution, 2025)

Regulatory mechanisms of trichome and root hair development in Arabidopsis - Muhammad Umair Yasin; Yihua Liu; Minjie Wu; Nana Chen; Yinbo Gan (Plant Molecular Biology, 2025)

Investigation of depositional fabric and its impact on the geomechanical behavior of limestones - Subhan Ullah; Muhammad Sajid; Khalid Latif; Abdul Rahim Asif; Muhammad Rizwan; Umair Mussawar; Shuja Ullah (Carbonates and Evaporites, 2025)

The introduction of the SARS-CoV-2 BA.4 lineage into Pakistan - Zaira Rehman; Katherine Edington; Zunera Jamal; Angelika Kritz-Wilson; Gytis Dudas; Samuel Sims; Richard Myers; Babak Afrough; Leena Inamdar; Syed Adnan Haider; Aamer Ikram; Muhammad Salman; et al. (Archives of Virology, 2025)

Nutraceutical Impact of Pumpkin Seed Oil on Expression Levels of EZH-2 and KRT-14 Genes against DSS-induced Inflammatory Bowel Disease in the Rat Model - Asma Mukhtar; Imran Mukhtar; Humaira Muzaffar; Muhammad Naeem Faisal; Kashif ur rehman khan; Laaraib Nawaz; Muhammad Umar Ijaz; Sana Maryam; Muhammad Umair; Haseeb Anwar; Farid S. Ataya; Gaber El-Saber Batiha; et al. (Cell Biochemistry and Biophysics, 2025)
Inflammatory bowel disease is a collection of intestinal disorders that cause inflammation in the digestive tract. Prolonged inflammation in the gastrointestinal tract is a major risk factor for colorectal cancer. The objective of this study was to fucus on gene expression levels of ( KRT-14 ; associated with epithelial cell integrity) and enhancer of zeste homolog-1 ( EZH-2; involved in cellular proliferation) in a IBD rat model in order to rule out impact of nutraceuticals (pumpkin seed oil; PSO) as a complementary approach to conventional treatments of IBD. In the current study, IBD was induced using dextran sodium sulfate (DSS). Following acclimatization, rats were separated into three groups: the negative control, the positive control, and the treatment group. The DSS (1 ml/kg bw) was given to the positive control and treatment groups. Negative control was given only a normal diet. Pumpkin seed oil (PSO) was given orally as a treatment (0.5 ml/kg bw). Blood and colon tissue were obtained on the 5 th , 10 th , 14 th, and 18 th days. Physical parameters, hematology, biochemical assays, gene expression, and histopathology were carried out. After statistical analyses, macroscopic parameters showed significant differences. Biochemical analyses revealed a significant ( P ≤ 0.05) decrease in serum potassium concentrations, total cholesterol, triglycerides, total proteins, total oxidants status, and C-reactive proteins in PSO treated group as compared with positive control. Gene expression levels of KRT-14 and EZH2 were significantly ( P ≤ 0.05) upregulated in PSO treated group as compared to positive control group. Histopathology revealed that pumpkin seed oil preserved the structural integrity of colon.

Titanium dioxide nanoparticles seed priming as a remedy for nickel-induced stress in maize through antioxidant enhancement and ultrastructural optimization - Muhammad Rehman; Abdul Salam; Bahar Ali; Irshan Ahmad; Muhammad Haseeb Javaid; Zulqarnain Haider; Raheel Munir; Muhammad Umair Yasin; Imran Ali; Chunyan Yang; Sajid Muhammad; Yinbo Gan (Journal of Environmental Management, 2025)

Food-derived phytochemicals from functional food (Allium sativum) as VEGF-R1 inhibitors: A novel approach for triple-negative breast cancer therapy - Abia Mahboob; Rashida Bashir; Ahmad Adnan; Muhammad Umer Khan; Umair Khurshid; Anjum Khursheed; Mhdia Elhadi Osman; Halima Mustafa Elagib; Nuha M.E. Agabna (Food Bioscience, 2025)

Nanosilica and salicylic acid synergistically regulate cadmium toxicity in rice - Sajid Muhammad; Zaid Ulhassan; Raheel Munir; Muhammad Umair Yasin; Faisal Islam; Kangni Zhang; Weiqi Chen; Mehmood Jan; Muhammad Afzal; Ali Muhammad; Fakhir Hannan; Weijun Zhou (Environmental Pollution, 2025)

Biomass derivatives photoreforming in pilot plant scale to obtain H2 under green conditions by using ball milling Cu2O-TiO2 P25 photocatalysts - Muhammad Umair; Alba Ruiz-Aguirre; Ilaria Berruti; Sixto Malato Rodríguez; Leonardo Palmisano; Vittorio Loddo; Marianna Bellardita (Chemical Engineering Journal, 2025)

Impact of biogenic zinc oxide nanoparticles on physiological and biochemical attributes of pea (Pisum sativum L.) under drought stress - Aneeza Ishfaq; Irfan Haidri; Usman Shafqat; Imran Khan; Muhammad Iqbal; Faisal Mahmood; Muhammad Umair Hassan (Physiology and Molecular Biology of Plants, 2025)

Techno-economic evaluation of solar photovoltaic power production in China for sustainable development and the environment - Yuhang Wang; Seoyeon Lee; Chuanyang Li; Muhammad Umair; Inobat Yakhyaeva (Environment, Development and Sustainability, 2024)

Integrative application of biochar and bacteria for mitigating antimony toxicity and bio-accessibility in sorghum - Muhammad Umair Hassan; Huifang Xu; Mansour Ghorbanpour; Yu Yongfang; Binjuan Yang; Quan Zhou; Tahir Abbas Khan; Huang Guoqin (Science of The Total Environment, 2024)

The pivotal role of arbuscular mycorrhizal fungi in enhancing plant biomass and nutrient availability under drought stress conditions: A global meta-analysis - Fawad Zaman; Muhammad Umair Hassan; Wajid Ali Khattak; Ahmad Ali; Mohamed F. Awad; Fu-Sheng Chen (Science of The Total Environment, 2024)

Bioderived carbon quantum dots boost maize growth and photosynthesis by augmenting UV spectrum absorption and carbon assimilation regulatory genes - Zulqarnain Haider; Chunyan Yang; Irshan Ahmad; Samta Zia; Muhammad Haseeb Javaid; Muhammad Rehman; Muhammad Umair Yasin; Bahar Ali; Chen Nana; Yinbo Gan (Journal of Environmental Chemical Engineering, 2024)

Encapsulation, optimization, and characterization of lycopene using soy protein isolate-peach gum conjugate as wall material - Arif Hussain; Muhammad Hussain; Waqas Ashraf; Khubaib Ali; Abid Hussain; Hsu Mon Phyo; Muhammad Umair Khalid; Mudassar Hussain; Zhang Lianfu (Food Bioscience, 2024)

Preparation, characterization, and antifungal capacity of Co-encapsulated anisaldehyde and cinnamaldehyde within pullulan-stabilized nanoemulsions for bread preservation - Muhammad Umair Khalid; Hsu Mon Phyo; Farazia Hassan; Anam Mushtaq; Arif Hussain; Mudassar Hussain; Tawfiq Alsulami; Weirong Yao (Food Bioscience, 2024)

Utilizing Cinnamomum verum (a culinary spice), as a functional food ingredient ameliorating hypercholesterolemia: In-vivo, in-vitro, and in-silico multi-model analysis - Mahnoor Bano; Muhammad Khurram Waqas; Talha Ali Chohan; Fakhra Batool; Aamir Mushtaq; Yahya I. Asiri; Mohd. Zaheen Hassan; Md Ali Mujtaba; Md. Khalid Anwer; Muhammad Irfan Sidique; Ayesha Riaz; Umair Khurshid; et al. (Food Bioscience, 2024)

2D Ti3C2Tx-MXene and its superstructures as dual-function electrodes for triboelectric nanogenerators for self-powered electronics - Shoaib Anwer; Muhammad Umair Khan; Anas Alazzam; Baker Mohammad; Eiyad Abu Nada (Chemical Engineering Journal, 2024)

Cobalt Ferrite@Barium titanate core-shell nanoparticles empowered triboelectric electromagnetic coupled nanogenerator for self-powered electronics - Fandi Jean; Muhammad Umair Khan; Shoaib Anwer; Anas Alazzam; Baker Mohammad (Chemical Engineering Journal, 2024)

Overexpression of Gossypium arboreum 3-ketoacyl-CoA synthase 6 (GaKCS6) gene enhanced leaf epicuticle wax in Gossypium hirsutum L. and improved tolerance against whitefly - Muhammad Umair Majid; Rabiah Ashraf; Basit Jabbar; Usman Arif; Fatima Batool; Sameera Hassan; Bushra Rashid (Biocatalysis and Agricultural Biotechnology, 2024)

Bioactivities of natural product geodin congeners and their preliminary structure activity relationship - Gulab Said; Amjad Ali; Muhammad Umair; Farooq Ahmad; Salma Gul; Muhammad Ateeq (Natural Product Research, 2024)

Evaluation of urban transportation carbon footprint − Artificial intelligence based solution - Huan Wang; Xinyu Wang; Yuanxing Yin; Xiaojun Deng; Muhammad Umair (Transportation Research Part D: Transport and Environment, 2024)

Capturing different modes of hydrogen combustion in a spark-ignition engine using numerical simulations - Muhammad Umair Manzoor; Xinbei Dou; MohammadReza Yosri; Mohsen Talei; Yi Yang (Fuel, 2024)

Assessment of natural radioactivity levels in rice samples and their implications for radiological protection - Hannan Younis; Mian Mateen Ullah; Muhammad Adil Khan; Farooq Ahmad; Umair Azeem; Muhammad Waseem; Khurram Mehboob; Muhammad Ajaz; Wazir Muhammad (Isotopes in Environmental and Health Studies, 2024)

Site Response Analysis Considering Site-Affects Leading to Seismic Microzonation Map of Lahore - Maham Basharat; Ajwat Mustafa; Muhammad Umar; Mehtab Alam; Umair Ali; Muhammad Irfan (Geotechnical and Geological Engineering, 2024)

Towards sustainable manufacturing: unpacking green practices’ impact on environmental performance in Pakistan - Muhammad Bilal; Zhao Xicang; Wu Jiying; Muhammad Umair Wattoo; Muhammad Adnan (Environment, Development and Sustainability, 2024)

Nutritional and medicinal plants as potential sources of enzyme inhibitors toward the bioactive functional foods: an updated review - Hammad Saleem; Anam Yaqub; Rabiya Rafique; Tahir Ali Chohan; Durr-e-Shahwar Malik; Muhammad Imran Tousif; Umair Khurshid; Nafees Ahemad; Ramasamy Ramasubburayan; Kannan RR Rengasamy (Critical Reviews in Food Science and Nutrition, 2024)

Multifaceted roles of zinc nanoparticles in alleviating heavy metal toxicity in plants: a comprehensive review and future perspectives - Muhammad Umair Hassan; Huang Guoqin; Naeem Ahmad; Tahir Abbas Khan; Muhammad Nawaz; Adnan Noor Shah; Adnan Rasheed; Tahani A. Y. Asseri; Sezai Ercisli (Environmental Science and Pollution Research, 2024)

Control of potato powdery scab with fluazinam, cyazofamid or bupirimate under field conditions in China - Liangang Mao; Haojie Shi; Muhammad Umair Sial; Lan Zhang; Lizhen Zhu; Chi Wu; Xingang Liu (Crop Protection, 2024)

Preparation of medium- and long-chain triacylglycerols rich in n-3 polyunsaturated fatty acids by bio-imprinted lipase-catalyzed interesterification - Xiaoqiang Zou; Imad Khan; Yanxi Wang; Mudassar Hussain; Bangzhi Jiang; Lei Zheng; Yuechao Pan; Jijie Hu; Muhammad Umair Khalid (Food Chemistry, 2024)

Synergistic inhibition effect of anisaldehyde and cinnamaldehyde (SAC) against Aspergillus species (A. flavus & A. niger) in vitro and on bread - Muhammad Umair Khalid; Hsu Mon Phyo; Yuhang Du; Khubaib Ali; Waqas Ashraf; Hang Yu; Imad Khan; Weirong Yao (Food Bioscience, 2024)

How does intercropping contribute to soil organic carbon accumulation? A global synthesis - Shujuan Li; Sha Ye; Zeqin Liu; Muhammad Umair Hassan; Guoqin Huang; Quan Zhou (Agriculture, Ecosystems & Environment, 2024)

Effect of biochar amendment on bacterial community and their role in nutrient acquisition in spinach (Spinacia oleracea L.) grown under elevated CO2 - Shoaib Ahmad; Adiba Khan Sehrish; Muhammad Umair; Markus W. Mirino; Shafaqat Ali; Hongyan Guo (Chemosphere, 2024)

Corrigendum to “Minor mining, major influence: Economic implications and policy challenges of artisanal gold mining” [Resour. Pol. 91 (2024) 104886] - Miaozhi Yu; Yifan Wang; Muhammad Umair (Resources Policy, 2024)

Effect of zinc fortified, arid and irrigated wheat varieties flour upon life history parameters of red flour beetle, Tribolium castaneum (Herbest) (Coleoptera: Tenebrionidae) - Muhammad Rizwan; Muhammad Yasin; Muhammad Tahir; Ammad Ahmad; Ansa Banazeer; Muhammad Babar Shahzad Afzal; Umair Sagheer (Journal of Stored Products Research, 2024)

Can urea-coated fertilizers be an effective means of reducing greenhouse gas emissions and improving crop productivity? - Muhammad Umair Hassan; Huang Guoqin; Muhammad Saleem Arif; Muhammad Salman Mubarik; Haiying Tang; Huifang Xu; Binjuan Yang; Quan Zhou; Awais Shakoor (Journal of Environmental Management, 2024)

Organic fertilisation enhances network complexity among bacteria, fungi, and protists by improving organic matter and phosphorus in acidic agricultural soils - Ke Li; Xiaoyi Xing; Shubin Wang; Rujia Liao; Muhammad Umair Hassan; Muhammad Aamer; Lorenzo Barbanti; Tianwang Wen; Huifang Xu (European Journal of Soil Biology, 2024)

Mitigating potential of polystyrene microplastics on bioavailability, uptake, and toxicity of copper in maize (Zea mays L.) - Muhammad Saad Bashir; Umair Saeed; Jawad Aslam Khan; Muhammad Saeed; Ghazala Mustafa; Riffat Naseem Malik (Environmental Pollution, 2024)

Effects of Withania somnifera (L.) Dunal in acute pulmonary pathophysiology in a rat model of smoke-induced lung injury and role of IRS-1 and SOX-2 - Sana Saleem; Imran Mukhtar; Hanan Y. Aati; Humaira Muzaffar; Haseeb Anwar; Musaddique Hussain; Maqsood Ahmad; Muhammad Umair; Kashif-ur-Rehman Khan (South African Journal of Botany, 2024)

Comprehensive chemical profiling with UHPLC-MS, in-vitro, in-silico, and in-vivo antidiabetic potential of Typha domingensis Pers; A novel source of bioactive compounds - Rizwana Dilshad; Kashif-ur-Rehman Khan; Rihana Dilshad; Saeed Ahmad; Huma Rao; Umair Khurshid; Sultan Ahmad; Maqsood Ahmad; Hafiz Muhammad Usman Abid; Muhammad Kashif Zaman; Rabia Nisar; Saharish Khaliq; et al. (South African Journal of Botany, 2024)

Integrated study for assessing groundwater dynamics of the Dehdan village, Haripur Basin, Pakistan - Umair Bin Nisar; Siddique Akhtar Ehsan; Muhammad Imran Rafiq; Muhammad Rizwan Mughal (Journal of Applied Geophysics, 2024)

Geospatial identification of possible rainwater harvesting locations within a high-altitude Gilgit River basin, Pakistan - Madiha Asif; Muhammad Yaseen; Syed Umair Shahid; Yasir Latif; Salma Anwar; Sohail Abbas (Theoretical and Applied Climatology, 2024)
The management of water resources is no longer an option but a necessity especially in countries with a high rate of population growth like Pakistan. Pakistan has a high-water scarcity, an extremely varying topography, and is also one of the countries encountering the problem of climate change. Therefore, prudent utilization of available water resources is a matter in the plains of Pakistan as in its high-altitude regions. Instead of wasting water which is a valuable resource, rainwater harvesting is a way of saving rainwater as an alternative source of fresh water for better use. The aim of this study was to search for potential rainwater-harvesting areas in a high-altitude Gilgit River basin. This research employed the SCS-CN technique in estimating surface runoff in the GIS environment. The geospatial study used four input parameters: slope of the land, land covers, surface runoff and drainage density. The research concluded that some lands, especially those that are deserted in dry area and agricultural lands, can serve as the sites of rainwater harvesting, with only 4% of area that was highly suitable for the purpose. Nevertheless, 37% of the investigated area was shown as totally unviable for rainwater collection installations because of steep slopes and substantial volume of snow. Simultaneously, the rainwater storage design solutions suggested were check dam, percolation tank, and agricultural ponds with the area of 3.5%, 1%, and 0.75% of the given land area, respectively, for rainwater harvesting. The locations of potential catchment and planned rainwater harvesting structures would assist the local authorities and the policy makers to provide plans and design on the construction of water storages and also the optimization of water use.

Green-synthesized lignin nanoparticles enhance Zea mays resilience to salt stress by improving antioxidant metabolism and mitigating ultrastructural damage - Muhammad Haseeb Javaid; Nana Chen; Muhammad Umair Yasin; Xingming Fan; Asifa Neelam; Muhammad Rehman; Zulqarnain Haider; Syed Asad Hussain Bukhari; Raheel Munir; Irshan Ahmad; Yinbo Gan (Chemosphere, 2024)

Balancing agricultural production and environmental sustainability: Based on Economic Analysis From North China Plain - Hongyu Shi; Muhammad Umair (Environmental Research, 2024)

Improving urban road infrastructure analysis and design using an integrated BIM-GIS and traffic microsimulation framework - Mohammad Sohaib; Aaqib Najeeb; Muhammad Umair; Muhammad Arsalan Khan; Muhammad Umer Zubair; Zulqarnain Jehan; Afaq Khattak (Innovative Infrastructure Solutions, 2024)

Electrochemical C-C coupling mediated by novel Sn-SnO2 supported Cu single atoms: The case of CO2 conversion to ethanol - Muhammad Aurang Zeb Gul Sial; Na Guo; Abdul Jalil; Muhammad Abbas; Muhammad Mateen; Sami Ullah; Umair Alam; Zahid Manzoor Bhat; Arshad Hussain; Xingke Cai; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Efficacy of Different Pre and Post Emergence Herbicide Application on Late Sown Maize Crop Under Variable Planting Density - Muhammad Talha Aslam; Rizwan Maqbool; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Zia Ul Haq; Muhammad Nauman Gulzar; Fatmah M. Alqahtani; Mohamed Hashem; Muhammad Umair Hassan; Sezai Ercisli (International Journal of Plant Production, 2024)

COVID-19 and the transformation of emerging economies: Financialization, green bonds, and stock market volatility - Wang Yiming; Liu Xun; Muhammad Umair; Assilova Aizhan (Resources Policy, 2024)

Cadmium induced defense enhance the invasive potential of Wedelia trilobata under herbivore infestation - Mohsin Nawaz; Jianfan Sun; Yanwen Bo; Feng He; Samina Shabbir; Muhammad Umair Hassan; Linxuan Pan; Parvaiz Ahmad; Christian Sonne; Daolin Du (Journal of Hazardous Materials, 2024)

Assessment of water quality using entropy-weighted quality index, statistical methods and electrical resistivity tomography, Moti village, northern Pakistan - Umair Bin Nisar; Wajeeh ur Rehman; Saher Saleem; Kashif Taufail; Faizan ur Rehman; Muhammad Farooq; Siddique Akhtar Ehsan (Journal of Contaminant Hydrology, 2024)

Genomic characterization of human respiratory syncytial virus circulating in Islamabad, Pakistan, during an outbreak in 2022-2023 - Syed Adnan Haider; Zunera Jamal; Faheem Tahir; Muhammad Salman; Massab Umair (Archives of Virology, 2024)

How causality impacts the renewable energy, carbon emissions, and economic growth nexus in the South Caucasus Countries? - Azer Dilanchiev; Muhammad Umair; Muhammad Haroon (Environmental Science and Pollution Research, 2024)

Study loss of vegetative cover and increased land surface temperature through remote sensing strategies under the inter-annual climate variability in Jinhua–Quzhou basin, China - Shahzad Ali; Abdul Basit; Sajid Ali; Muhammad Umair; Tyan Alice Makanda; Mohammed Rafi Shaik; Mujeeb Khan (Environmental Science and Pollution Research, 2024)

The synergistic potential of biochar and nanoparticles in phytoremediation and enhancing cadmium tolerance in plants - Muhammad Umair Yasin; Zulqarnain Haider; Raheel Munir; Usman Zulfiqar; Muhammad Rehman; Muhammad Haseeb Javaid; Irshan Ahmad; Chen Nana; Muhammad Sulaman Saeed; Bahar Ali; Yinbo Gan (Chemosphere, 2024)

RETRACTED: Minor mining, major influence: Economic implications and policy challenges of artisanal gold mining - Miaozhi Yu; Yifan Wang; Muhammad Umair (Resources Policy, 2024)

Aspects of superior photocatalytic dye degradation and adsorption efficiency of reduced graphene oxide multiwalled carbon nanotubes with modified ZnO-Al2O3 nanocomposites - Ajaz Ahmad Wani; Ryhan Abdullah Rather; Norazuwana Shaari; Umair Khan; Taseer Muhammad; Syed Modassir Hussain; Laila F. Seddek; Ahmed M. Abed (Journal of Environmental Chemical Engineering, 2024)

Remimazolam versus propofol for sedation in gastrointestinal endoscopy and colonoscopy within elderly patients: a meta-analysis of randomized controlled trials - Wania Ahmer; Sahar Imtiaz; Daniyal Muhammad Alam; Khadija Ahmed; Barka Sajid; Juvairia Yousuf; Sunny Asnani; Muhammad Ahmed Ali Fahim; Rahmeen Ali; Marium Mansoor; Muhammad Talha Safdar; Muhammad Umair Anjum; et al. (European Journal of Clinical Pharmacology, 2024)

Impacts of climate and land coverage changes on potential evapotranspiration and its sensitivity on drought phenomena over South Asia - Shahzad Ali; Abdul Basit; Muhammad Umair; Jian Ni (International Journal of Climatology, 2024)
Understanding the spatiotemporal historical drought pattern and their sensitivity effect on potential evapotranspiration (PET) and vegetation coverage changes is essential for efficient drought mitigation policies under climate change. In this study, we used the standardized precipitation evapotranspiration index (SPEI) at multiple timescales, such as SPEI‐01, SPEI‐03, SPEI‐06, SPEI‐09 and SPEI‐12; we explored their regional‐scale dry and wet annual changes across seven sub‐regions of South Asia from 1902 to 2018. Results suggest that from 1981 to 2018, the extreme drought of SPEI has increased in South Asia, which mostly affects the summer and winter growing seasons, that is, SPEI‐06 to SPEI‐12 across seven sub‐regions of South Asia. The frequency of drought events during dry and wet annual changes of SPEI had an extremely dry year starting from 1998 to 2018, which mostly affected the South Asia region. Data from the past 18 years showed that the land changing detection has increased in the forests, cultivated land, arid land, savanna and farmland; by contrast, there has been significantly reduced permanent ice and snow, mixed forests, open shrub, grasslands, permanent wetlands, water bodies and evergreen broadleaf forests. Seasonal SPEI presented diverse characteristics such as showing a dry trend in Afghanistan, India, Pakistan and Sri Lanka during autumn and winter. Afghanistan and Bhutan are wet during the summer compared with other sub‐regions of South Asia, with drought frequency occurring at 45.3% and 44.4%. Sri Lanka, Pakistan and India are the driest regions in South Asia due to their high drought frequency, duration and intensity. The correlation between PET and crop water stress index (CWSI), PET and regional ET p reduction (Er) indicated a considerably negative correlation, while a significantly positive correlation was found between CWSI and Er, NDVI and Er. This study provides a comprehensive assessment of climate and vegetation coverage changes on PET, ET and SPEI, and can help in formulating long‐term adaptive strategies to reduce the cumulative impacts of droughts.

Efficient treatment of veterinary pharmaceutical industrial wastewater by catalytic ozonation process: degradation of enrofloxacin via molecular ozone reactions - Amir Ikhlaq; Zafar Masood; Umair Yaqub Qazi; Muhammad Raashid; Osama Shaheen Rizvi; Hafiz Abdul Aziz; Muhammad Saad; Fei Qi; Rahat Javaid (Environmental Science and Pollution Research, 2024)

Interactive mode of biochar-based silicon and iron nanoparticles mitigated Cd-toxicity in maize - Muhammad Umair Yasin; Fakhir Hannan; Raheel Munir; Sajid Muhammad; Muhammad Iqbal; Iqra Yasin; Muhammad Saad Shoaib Khan; Farah Kanwal; Yang Chunyan; Xingming Fan; Yinbo Gan (Science of The Total Environment, 2024)

Influence of lunar phases and meteorological factors on rainfall in Karachi City, Pakistan - Umair Rasool; Xinan Yin; Zongxue Xu; Muhammad Awais Rasool; Mureed Hussain; Farhan Iftikhar (Journal of Hydrology, 2024)

MOFs coupled transition metals, graphene, and MXenes: Emerging electrocatalysts for hydrogen evolution reaction - Abdul Hanan; Muhammad Nazim Lakhan; Faiza Bibi; Amjad Khan; Irfan Ali Soomro; Altaf Hussain; Umair Aftab (Chemical Engineering Journal, 2024)

Integration of chitosan coating and short-term hypobaric treatment extends postharvest life and upregulates defense-related enzymes in apple fruit - Syed Umair Shah; Majid S. Hashmi; Muhammad Rafiullah Khan; Ayaz Ahmad; Aysha Riaz; Yosef Al Shoffe; Said Wahab; Muhammad Ayub; Antonio Ippolito (European Journal of Plant Pathology, 2024)

Melatonin alleviated cadmium accumulation and toxicity by modulating phytohormonal balance and antioxidant metabolism in rice - Raheel Munir; Muhammad Umair Yasin; Muhammad Afzal; Mehmood Jan; Sajid Muhammad; Nazia Jan; Chen Nana; Faisal Munir; Hamza Iqbal; Faiza Tawab; Yinbo Gan (Chemosphere, 2024)

RETRACTED: Synergistic effect of silicon and arbuscular mycorrhizal fungi reduces cadmium accumulation by regulating hormonal transduction and lignin accumulation in maize - Shah Rukh Khan; Zubair Ahmad; Zeeshan Khan; Umair Khan; Muhammad Asad; Tariq Shah (Chemosphere, 2024)

New insights into the environmental application of hybrid nanoparticles in metal contaminated agroecosystem: A review - Muhammad Umair; Sehrish Huma Zafar; Mumtaz Cheema; Muhammad Usman (Journal of Environmental Management, 2024)

2D Ti3C2Tx-MXene nanosheets and graphene oxide based highly sensitive humidity sensor for wearable and flexible electronics - Waqas Waheed; Shoaib Anwer; Muhammad Umair Khan; Muhammad Sajjad; Anas Alazzam (Chemical Engineering Journal, 2024)

Cassia Angustifolia Primed ASCs Accelerate Burn Wound Healing by Modulation of Inflammatory Response - Saba Tasneem; Hafiz Ghufran; Maryam Azam; Amna Arif; Musab Bin Umair; Muhammad Amin Yousaf; Khurrum Shahzad; Azra Mehmood; Kausar Malik; Sheikh Riazuddin (Tissue Engineering and Regenerative Medicine, 2024)

A practical tool for structural design optimization of steel frames: development and application for parametric analysis - Umair Ali; Rizwan Azam; Mansoor Shakeel; Muhammad Adil; Muhammad Rizwan Riaz (Innovative Infrastructure Solutions, 2024)

The effect of winter crop incorporation on greenhouse gas emissions from double rice-green manure rotation in South China - Haiying Tang; Ying Liu; Jingyi Li; Jianqun Miao; Muhammad Nawaz; Basharat Ali; Shafaqat Ali; Muhammad Aamer; Muhammad Umair Hassan; Guoqin Huang (Environmental Science and Pollution Research, 2023)

Crude oil security in a turbulent world: China's geopolitical dilemmas and opportunities - Huiai Yuan; Lihong Zhao; Muhammad Umair (The Extractive Industries and Society, 2023)

Geocellular Modeling of the Cambrian to Eocene Multi-Reservoirs, Upper Indus Basin, Pakistan - Muhsan Ehsan; Muhammad Ali Umair Latif; Abid Ali; Ahmed E. Radwan; Muhammad Attique Amer; Kamal Abdelrahman (Natural Resources Research, 2023)

Exogenous Application of Silicon and Sulfate Improved Drought Tolerance in Sunflowers Through Modulation of Morpho-physiological and Antioxidant Defense Mechanisms - Muhammad Nisar; Muhammad Aqeel; Abdul Sattar; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Umair Rasheed; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Fahad Mohammed Alzuaibr; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2023)

Development of Aluminium (Al)-Tolerant Soybean Using Molecular Tools: Limitations and Future Directions - Adnan Rasheed; Anwar Ahmad Khan; Muhammad Nawaz; Athar Mahmood; Uzma Arif; Muhammad Umair Hassan; Javed Iqbal; Muhammad Hamzah Saleem; Basharat Ali; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Different Rotation and Double Straw Returning Significantly Increase Liable Organic Carbon Content and Yield of Double Cropping Paddy Field in Southern China - Zhiqiang Wang; Haiying Tang; Guoqin Huang; Jianqun Miao; Ying Liu; Adnan Noor Shah; Muhammad Nawaz; Muhammad Ahsin Ayub; Muhammad Umair Hassan (International Journal of Plant Production, 2023)

A comprehensive study of the sources, extraction methods and structures of the Saponin compounds for its antidiabetic activity - Muhammad Umair Afzal; Muhammad Pervaiz; Anam Ejaz; Eisha Bajwa; Sadaf Naz; Zohaib Saeed; Sami Ullah; Syeda Shaista Gillani; Rana Rashad Mehmood Kan; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Investigating the effects of matrix acidizing and acid fracturing on the production optimization of a carbonate reservoir: a case study - Umair Qureshi; Haris Ahmed Qureshi; Amanat Ali Bhatti; Muhammad Salman Saeed; Muhammad Sameer Khalid (Arabian Journal of Geosciences, 2023)

Unraveling the effects of zinc sulfate nanoparticles and potassium fertilizers on quality of maize and associated health risks in Cd contaminated soils under different moisture regimes - Muhammad Umair; Sehrish Huma Zafar; Mumtaz Cheema; Rashid Minhas; Abdul Manan Saeed; Muhammad Saqib; Muhammad Aslam (Science of The Total Environment, 2023)

Optimizing organizational performance in manufacturing: The role of IT capability, green supply chain integration, and green innovation - Adnan Abbas; Xiaoguang Luo; Fakhar Shahzad; Muhammad Umair Wattoo (Journal of Cleaner Production, 2023)

Edge-hosted CoFeB active sites with graphene nanosheets for highly selective nitrogen reduction reaction towards ambient ammonia synthesis - Muhammad Arif; Anuj Kumar; Muhammad Asim Mushtaq; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Unaiza Talib; Saira Ajmal; Khalid M. Alotaibi; Ghulam Yasin (Chemical Engineering Journal, 2023)

Validation of the environmental Kuznets curve and role of economic globalization: an aggregate and sectoral analysis of an Indian economy - Ashfaq Ahmad; Muhammad Mobeen Shafqat; Muhammad Ilyas; Muhammad Umair Ashraf; Afshan Urooj; Zhao Yu huan (Air Quality, Atmosphere & Health, 2023)

The impact of financial innovation, green energy, and economic growth on transport-based CO2 emissions in India: insights from QARDL approach - Snovia Naseem; Umair Kashif; Yasir Rasool; Muhammad Akhtar (Environment, Development and Sustainability, 2023)

Water quality, governance issues, people's perception and water distribution network management through integrated techniques under changing climate - Toqeer Ahmed; Mumtaz Ahmed; Saima Naz; Umair Bin Nisar; Muhammad Zahir (Urban Climate, 2023)

The protective nature of gold during times of oil price volatility: An analysis of the COVID-19 pandemic - Yu Li; Muhammad Umair (The Extractive Industries and Society, 2023)

Variants in FREM1 and trisomy 18 identified in a neonatal progeria patient - Saima Siddiqi; Noor ul Ain; Mehran Kauser; Zahra Mukhtar; Muhammad Ansar; Muhammad Umair (Molecular Biology Reports, 2023)

Neem and Castor Oil–Coated Urea Mitigates Salinity Effects in Wheat by Improving Physiological Responses and Plant Homeostasis - Imran Khan; Sadia Muhammad Ali; Muhammad Umer Chattha; Lorenzo Barbanti; Roberta Calone; Athar Mahmood; Tasahil S. Albishi; Muhammad Umair Hassan; Sameer H. Qari (Journal of Soil Science and Plant Nutrition, 2023)
Soil salinity is abiotic stress of growing concern, whose effects can be potentially mitigated by the use of suitable fertilisers. Based on this, an experiment was conducted to determine the role of vegetable oil–coated urea on the performance of wheat ( Triticum aestivum ) under salinity. Neem oil–coated urea (NOCU), castor oil–coated urea (COCU), and normal urea (NU) were compared in wheat plants growing in pots at three soil salinity levels (0, 6, and 12 dS m -1 ). Plant morphology, growth, element contents (Na, Cl, K, and N), and several traits were assessed at the flag leaf stage; biological yield, grain yield, and its components were assessed at maturity. Salinity stunted growth (approximately -50% yield with high salinity vs. control); boosted Na and Cl concentrations while abating K and N concentrations in plant organs; impaired leaf water status; reduced photosynthetic pigments and increased antioxidant activities and osmo-regulating compounds. NOCU and, to a lesser degree, COCU mitigated salinity effects by upgrading antioxidant activities, reducing oxidative stress markers, increasing leaf water status, photosynthetic pigments, and osmo-regulating compounds. However, NOCU under high salinity could only achieve the levels of NU under intermediate salinity. Lastly, NOCU and COCU restricted plant entry of adverse ions (Na and Cl) while increasing K and N accumulation. Vegetable oil–coated urea, namely NOCU, significantly contributed to improving wheat behaviour and final yield under salinity. These outcomes are associated with the two fertilisers’ properties of slow nitrogen release.

Exploring the nexus between monetary uncertainty and volatility in global crude oil: A contemporary approach of regime-switching - Mengyan Yu; Muhammad Umair; Yessengali Oskenbayev; Zhаnsaya Karabayeva (Resources Policy, 2023)

Engineering of electrodes with 2D Ti3C2Tx-MXene sheets and chloride salt for robust and flexible high electrical power triboelectric nanogenerator - Shoaib Anwer; Muhammad Umair Khan; Baker Mohammad; Moh'd Rezeq; Wesley Cantwell; Dongming Gan; Lianxi Zheng (Chemical Engineering Journal, 2023)

Trehalose: A Key Player in Plant Growth Regulation and Tolerance to Abiotic Stresses - Muhammad Umair Hassan; Muhammad Nawaz; Adnan Noor Shah; Ali Raza; Lorenzo Barbanti; Milan Skalicky; Mohamed Hashem; Marian Brestic; Saurabh Pandey; Saad Alamri; Yasser S. Mostafa; Ayman E. L. Sabagh; et al. (Journal of Plant Growth Regulation, 2023)

Spectroscopic fingerprinting, pollution characterization, and health risk assessment of potentially toxic metals from urban particulate matter - Abdul Rehman; Guijian Liu; Balal Yousaf; Samra Ijaz; Samina Irshad; Ayesha Imtiyaz Cheema; Muhammad Umair Riaz; Aniqa Ashraf (Environmental Science and Pollution Research, 2023)

Phytochemical, biological, and in-silico analysis of Colutea armata Hemsl. & Lace: A possible source of bioactive natural compounds - Ayisha Khalid; Samina Afzal; Farhan Abbas; Iftikhar Afzal; Muhammad Iqbal; Sarfraz Ahmad; Siddique Akber Ansari; Hamad M. Alkahtani; Tahir Ali Chohan; Umair Khurshid; Hammad Saleem; Carlos Leonardo Cespedes-Acuna (South African Journal of Botany, 2023)

Removal of pharmaceutically active compounds from water sources using nanofiltration and reverse osmosis membranes: Comparison of removal efficiencies and in-depth analysis of rejection mechanisms - Asif Matin; Shehzada Muhammad Sajid Jillani; Umair Baig; I. Ihsanullah; Khalid Alhooshani (Journal of Environmental Management, 2023)

Normal and knocking combustion of hydrogen: A numerical study - Muhammad Umair Manzoor; MohammadReza Yosri; Mohsen Talei; Farzad Poursadegh; Yi Yang; Michael Brear (Fuel, 2023)

Sedimentology and reservoir characteristics of Jurassic Samanasuk Formation of Salt Range and Hazara areas, Upper Indus Basin, Pakistan - Syed Umair Ali; Syed Kamran Ali; Khawaja Umair Majeed; Muhammad Haris; Muhammad Zaheer; Tariq Mehmood (Arabian Journal of Geosciences, 2023)

Development of high-capacity surface-engineered MXene composite for heavy metal Cr (VI) removal from industrial wastewater - Umair Ali Asif; Khalid Mahmood; Salman Raza Naqvi; Muhammad Taqi Mehran; Tayyaba Noor (Chemosphere, 2023)

In vitro-produced equine blastocysts exhibit dispersed ICM cell allocation - Muhammad Umair; Anthony N Claes; Verônica F da Cunha Scheeren; Mabel M Beitsma; Silvia Colleoni; Cesare Galli; Giovanna Lazzari; Marta de Ruijter-Villani; Tom A Stout (Journal of Equine Veterinary Science, 2023)

Electronic structure and oxygen vacancy tuning of Co & Ni co-doped W18O49 nanourchins for efficient TEA gas sensing - Shah Zeb; Zhen Yang; Riming Hu; Muhammad Umair; Saira Naz; Yu Cui; Chengyuan Qin; Tongyao Liu; Xuchuan Jiang (Chemical Engineering Journal, 2023)

Controlling Arsenic Contamination Through Bentonite Clays: a Batch Sorption Study - Muhammad Umair; Ayaz Mehmood; Shah Rukh; Ahmad Khan; Zahoor Ahmad; Mazhar Rafique; Kouser Majeed Malik; Ali Raza Gurmani (Journal of Soil Science and Plant Nutrition, 2023)

Effects of Winter Cropping on rice Yield, Economic Benefit, and Resource Utilization Efficiency on Different Cropping Systems of Paddy Field in the Middle Reaches of the Yangtze River - Haiying Tang; Guiyuan Meng; Wenjie Jiang; Ying Liu; Athar Mahmood; Adnan Noor Shah; Muhammad Nawaz; Muhammad Umair Hassan; Guoqin Huang (International Journal of Plant Production, 2023)

Examining the interconnectedness of green finance: an analysis of dynamic spillover effects among green bonds, renewable energy, and carbon markets - YaFei Zhang; Muhammad Umair (Environmental Science and Pollution Research, 2023)

Evaluating the relationship between groundwater quality and land use in an urbanized watershed - Umair Rasool; Xinan Yin; Zongxue Xu; Muhammad Faheem; Muhammad Awais Rasool; Jamil Siddique; Muhammad Azher Hassan; Venkatramanan Senapathi (Environmental Science and Pollution Research, 2023)

Rainfall-driven machine learning models for accurate flood inundation mapping in Karachi, Pakistan - Umair Rasool; Xinan Yin; Zongxue Xu; Roberta Padulano; Muhammad Awais Rasool; Muhammad Amir Siddique; Muhammad Azher Hassan; Venkatramanan Senapathi (Urban Climate, 2023)

Public-sector participation in the circular economy: A stakeholder relationship analysis of economic and social factors of the recycling system - Muhammad Umair Shah; Ryan Rezai (Journal of Cleaner Production, 2023)

Detrimental effects of Cd and temperature on rice and functions of microbial community in paddy soils - Raheel Munir; Mehmood Jan; Sajid Muhammad; Muhammad Afzal; Nazia Jan; Muhammad Umair Yasin; Iqbal Munir; Aqib Iqbal; Shuaiqi Yang; Weijun Zhou; Yinbo Gan (Environmental Pollution, 2023)

Revisiting the environmental impact of renewable energy, non-renewable energy, remittances, and economic growth: CO2 emissions versus ecological footprint for top remittance-receiving countries - Muhammad Umair; Muhammad Uzair Yousuf; Jabbar Ul-Haq; Zahid Hussain; Hubert Visas (Environmental Science and Pollution Research, 2023)

Spinach-derived boron-doped g-C3N4/TiO2 composites for efficient photo-degradation of methylene blue dye - Sadia Faryad; Umair Azhar; Muhammad Bilal Tahir; Wahid Ali; Muhammad Arif; Muhammad Sagir (Chemosphere, 2023)

Graphene loaded TiO2 submicron spheres scattering layer for efficient dye-sensitized solar cell - Muhammad Umair Shahid; Norani Muti Mohamed; Ali Samer Muhsan; Siti Nur Azella Zaine; Mehboob Khatani; Asfand Yar; Waqar Ahmad; Muhammad Babar Hussain; Asma A. Alothman; Mohammed Sheikh Saleh Mushab (Chemosphere, 2023)

A comprehensive review on the botany, traditional uses, phytochemistry, pharmacology and toxicity of Anagallis arvensis (L).: A wild edible medicinal food plant - Hammad Saleem; Umair Khurshid; Muhammad Imran Tousif; Sirajudheen Anwar; Nasser A. Awadh Ali; Mohamad Fawzi Mahomoodally; Nafees Ahemad (Food Bioscience, 2023)

Exogenous application of melatonin alleviates the drought stress by regulating the antioxidant systems and sugar contents in sorghum seedlings - Ahmad Sher; Muhammad Umair Hassan; Abdul Sattar; Sami Ul-Allah; Muhammad Ijaz; Zara Hayyat; Yamin Bibi; Mubashar Hussain; Abdul Qayyum (Biochemical Systematics and Ecology, 2023)

Does economic fitness matter in carbon emissions mitigation in BRICS countries? - Jabbar Ul-Haq; Hubert Visas; Muhammad Umair; Zahid Hussain; Sana Khanum (Environmental Science and Pollution Research, 2023)

Assessing oil price volatility co-movement with stock market volatility through quantile regression approach - Fang Liu; Muhammad Umair; Junjun Gao (Resources Policy, 2023)

Synthesis of co-polyamide reverse osmosis membrane constituting a linear aliphatic triamine and m-phenylenediamine for enhanced desalination performance - Abdul Waheed; Umair Baig; Asif Matin; Shehzada Muhammad Sajid Jillani; Naef A.A. Qasem; Isam H. Aljundi (Desalination, 2023)

Sedimentological and Petrographical Characterization of the Cambrian Abbottabad Formation in Kamsar Section, Muzaffarabad Area: Implications for Proto-Tethys Ocean Evolution - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Tariq Mehmood; Khawaja Umair Majeed (Journal of Marine Science and Engineering, 2023)
The current sedimentological and petrographical research of the Abbottabad Formation has been carried out in order to understand the formation and evolution of the Proto-Tethys Ocean during the Cambrian on the northern margin of the Indian Plate. The Muzaffarabad region is located east of the Upper Indus Basin and the southern part of the Hazara Kashmir Syntaxis. The geological history of the region varies from the Precambrian to the recent period. The Cambrian Abbottabad Formation is well exposed along the Hazara Kashmir Syntaxis at the core of the 500-m-thick Muzaffarabad anticline. The Abbottabad Formation is an unconformity-bounded allo-stratigraphic unit. It has an unconformable lower contact with the Late Precambrian Dogra Formation and an unconformable upper contact with the Paleocene Hangu Formation. The Abbottabad Formation has been divided into four lithofacies, from bottom to top, namely, thinly interbedded dolomite and shale, cherty-stromatolitic dolomite, oxidized limonitic-brecciated zone, and quartzite, with significant lithological changes. Petrographic studies revealed four types of dolomites: fine crystalline dolomite (Dol. I), dolomitic cryptocrystalline chert (Dol. II), algal mat-stromatolitic dolomite (Dol. III), and intraclastic-dolo-grain stone (Dol. IV). The mineral composition of dolostone was analyzed using X-ray diffraction (XRD) and found to be consistent with previous petrographic studies. The dolomite mineral content decreased from base to top, while chert increased towards the top. Elemental weight percentages through energy dispersive X-ray (EDX) analysis show different elements constitute the minerals found in the dolostone, as confirmed by petrographic and XRD analysis. Using outcrop data, facies information, and geochemical data, a modified depositional model of the Abbottabad Formation was developed. During the Early Cambrian period, the formation was deposited in a shallow subtidal to supratidal setting of the Proto-Tethys Ocean. The top of this deposit marks the Cambrian–Paleocene boundary. Because of the progressively coarsening outcrop sequences, this formation seems to be at the very top of the Proto-Tethys Ocean’s shallow marine system.

Comparison of pennywort and hyacinth in the development of membraned sediment plant microbial fuel cell for waste treatment - Gull Wareen; Maimona Saeed; Noshin Ilyas; Saira Asif; Muhammad Umair; R.Z. Sayyed; Saleh Alfarraj; Wafa A. Alrasheed; Tahir Hussain Awan (Chemosphere, 2023)

Effect of farmyard manure, elemental sulphur and EDTA on growth and phytoextraction of cadmium by spider plants (Chlorophytum comosum L.) under Cd stress - Muhammad Zia-ur-Rehman; Arisha Mubsher; Muhammad Rizwan; Muhammad Usman; Muhammad Jafir; Muhammad Umair; Hesham F. Alharby; Atif A. Bamagoos; Rahma Alshamrani; Shafaqat Ali (Chemosphere, 2023)

How does dolomite application affect the greenhouse gases emissions from the terrestrial environment? – A global synthesis - Muhammad Umair Hassan; Maria Batool; Taimoor Hassan Farooq; Muhammad Saleem Arif; Muhammad Aamer; Muhammad Ahmed Waqas; Gadah Albasher; Maryium Sajjad; Awais Shakoor (Fuel, 2023)

Rational design and modulation strategies of Mo-based electrocatalysts and photo/electrocatalysts towards nitrogen reduction to ammonia (NH3) - Muhammad Arif; Muhammad Babar; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Asim Mushtaq; Ghulam Yasin; Muhammad Mubashir; Jun Wei Roy Chong; Kuan Shiong Khoo; Pau Loke Show (Chemical Engineering Journal, 2023)

Drought Stress in Brassica napus: Effects, Tolerance Mechanisms, and Management Strategies - Maria Batool; Ali Mahmoud El-Badri; Muhammad Umair Hassan; Yang Haiyun; Wang Chunyun; Yan Zhenkun; Kuai Jie; Bo Wang; Guangsheng Zhou (Journal of Plant Growth Regulation, 2023)

Evaluating the symmetric and asymmetric effects of fossil fuel energy consumption and international capital flows on environmental sustainability: a case of South Asia - Muhammad Umair; Muhammad Uzair Yousuf (Environmental Science and Pollution Research, 2022)

Trehalose: a promising osmo-protectant against salinity stress—physiological and molecular mechanisms and future prospective - Muhammad Nawaz; Muhammad Umair Hassan; Muhammad Umer Chattha; Athar Mahmood; Adnan Noor Shah; Mohamed Hashem; Saad Alamri; Maria Batool; Adnan Rasheed; Maryam A. Thabit; Haifa A. S. Alhaithloul; Sameer H. Qari (Molecular Biology Reports, 2022)

Leaf Area Regulates the Growth Rates and Seed Yield of Soybean (Glycine max L. Merr.) in Intercropping System - Muhammad Ali Raza; Hina Gul; Ali Hasnain; Muhammad Hayder Bin Khalid; Sajad Hussain; Ghulam Abbas; Waqas Ahmed; Muhammad Jawad Babar; Zaheer Ahmed; Amjad Saeed; Muhammad Umair Riaz; Azeem Iqbal Khan; et al. (International Journal of Plant Production, 2022)

Tanneries impact on groundwater quality: a case study of Kasur city in Pakistan - Hafiz Qasim Ali; Muhammad Umair Yasir; Amir Farooq; Mahrukh Khan; Muhammad Salman; Muhammad Waqar (Environmental Monitoring and Assessment, 2022)

Impact assessment of drought monitoring events and vegetation dynamics based on multi-satellite remote sensing data over Pakistan - Shahzad Ali; Abdul Basit; Jian Ni; Manzoor; Fahim Ullah Khan; Muhammad Sajid; Muhammad Umair; Tyan Alice Makanda (Environmental Science and Pollution Research, 2022)

Thiourea Application Improves the Growth and Seed and Oil Yields in Canola by Modulating Gas Exchange, Antioxidant Defense, and Osmoprotection Under Heat Stress - Muhammad Ahmad; Ejaz Ahmad Waraich; Usman Zulfiqar; Saddam Hussain; Muhammad Umair Yasin; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2022)

Energy, exergy, economic, environmental, energoeconomic, exergoeconomic, and enviroeconomic (7E) analyses of wind farms: a case study of Pakistan - Muhammad Uzair Yousuf; Muhammad Adil Abbasi; Muhammad Kashif; Muhammad Umair (Environmental Science and Pollution Research, 2022)

The scaling of leaf nitrogen and phosphorus along a phosphorus availability gradient in a subtropical forest - Jiahao Wen; Janice Brahney; Yaoben Lin; Zhiliang Ma; Ningxiao Sun; Ji Zheng; Huawei Ji; Hongzhang Kang; Baoming Du; Guopeng Liang; Muhammad Umair; Chunjiang Liu (Plant Ecology, 2022)

Hydrogen peroxide priming alleviates salinity induced toxic effect in maize by improving antioxidant defense system, ionic homeostasis, photosynthetic efficiency and hormonal crosstalk - Muhammad Umer Chattha; Muhammad Uzair Ul Hassan; Imran Khan; Muhammad Nawaz; Adnan Noor Shah; Abdul Sattar; Mohamed Hashem; Saad Alamri; Muhammad Talha Aslam; Haifa A. S. Alhaithloul; Muhammad Umair Hassan; Sameer H. Qari (Molecular Biology Reports, 2022)

CRISPR/Cas9 is a powerful tool for precise genome editing of legume crops: a review - Adnan Rasheed; Aminah A. Barqawi; Athar Mahmood; Muhammad Nawaz; Adnan Noor Shah; Daniyah H. Bay; Maryam A. Alahdal; Muhammad Umair Hassan; Sameer H. Qari (Molecular Biology Reports, 2022)

Comprehensive characterization of Guanosine monophosphate synthetase in Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Sajid Fiaz; Muhammad Imran; Ke Yanguo; Waseem Hassan; Umair Ashraf; Yuansheng He; Xuanjie Cai; Zhijiang Wang; Lei Yu; Xianwen Ye; et al. (Molecular Biology Reports, 2022)

Electrical resistivity tomography for delineating groundwater potential zones in fractured metasedimentary rocks, Lesser Himalayas, Pakistan - Muhammad Farooq; Umair Bin Nisar; Sarfraz Khan; Tarib Jalees; Muhammad Rizwan Mughal; Liaqat Ali; Toqeer Ahmed (Journal of Earth System Science, 2022)

Performance of Wheat Cultivars Under Different Tillage and Crop Establishment Methods - Muhammad Mahmood Iqbal; Imran Khan; Muhammad Umer Chattha; Muhammad Umair Hassan; Muhammad Iqbal; Muhammad Farooq (International Journal of Plant Production, 2022)

Viruses as tools in gene therapy, vaccine development, and cancer treatment - Musab bin Umair; Fujimura Nao Akusa; Hadia Kashif; Seerat-e-Fatima; Fatima Butt; Marium Azhar; Iqra Munir; Muhammad Ahmed; Wajeeha Khalil; Hafiz Sharyar; Shazia Rafique; Muhammad Shahid; et al. (Archives of Virology, 2022)

Recent approaches on the optimization of biomass gasification process parameters for product H2 and syngas ratio: a review - Muhammad Zain Siddiqui; Mahshab Sheraz; Umair Ali Toor; Ali Anus; Abid Mahmood; Muhammad Haseeb; Muhammad Ibrahim; Kuan Shiong Khoo; Vishno Vardhan Devadas; Muhammad Mubashir; Sami Ullah; Pau Loke Show (Environment, Development and Sustainability, 2022)

Photocatalytic degradation of methylene blue using polyaniline-based silver-doped zinc sulfide (PANI-Ag/ZnS) composites - Sidra Mazhar; Umair Yaqub Qazi; Nimra Nadeem; Muhammad Zahid; Abdul Jalil; Fareeda Khan; Iftikhar Ul-Hasan; Imran Shahid (Environmental Science and Pollution Research, 2022)

A Novel Visual-Range Sea Image Dataset for Sea Horizon Line Detection in Changing Maritime Scenes - Manzoor Ahmed Hashmani; Muhammad Umair (Journal of Marine Science and Engineering, 2022)
Sea horizon line (SHL) detection plays a pivotal role in the computational performance improvement of computer applications for the maritime environment by dividing the image into sea and sky regions. This division isolates the region of interest and reduces the computational cost of further processing. Testing and performance evaluation of SHL detection methods require a robust image dataset covering the maritime environment’s features at different geographical, seasonal, and maritime conditions. However, publicly available maritime image datasets are developed under a limited environment with slight-to-moderate variations in maritime features. This article proposes a novel sea image dataset that fills this gap by incorporating various geographical, seasonal, and maritime features. Across West Malaysia, one offshore and four geographically separated onshore locations were selected. On ten different occasions, field observations were recorded using a visual-range optical sensor and weather station. The data collection experiments were conducted between February 2020 until April 2021. The collected data were preprocessed and SHL images were selected based on their high feature diversity. Manual SHL annotation was applied on images, and a ground truth matrix was generated, which serves as a performance benchmark for SHL detection methods. As a result, the dataset presents 2673 high-definition (1920 × 1080 pixels) RGB images having a combination of 36 different geographical, seasonal, and maritime features to test and evaluate computer vision-based SHL detection methods.

Characterization of Mercury-Resistant Rhizobacteria for Plant Growth Promotion: An In Vitro and In Silico Approach - Aatif Amin; Muhammad Naveed; Umair Munawar; Arslan Sarwar; Zakia Latif (Current Microbiology, 2021)

Geospatially analysing the dynamics of the Khurdopin Glacier surge using multispectral and temporal remote sensing and ground observations - Muhammad Imran; Umair Ahmad (Natural Hazards, 2021)

Foliar Manganese Supply Enhances Crop Productivity, Net Benefits, and Grain Manganese Accumulation in Direct-Seeded and Puddled Transplanted Rice - Usman Zulfiqar; Saddam Hussain; Muhammad Ishfaq; Nauman Ali; Muhammad Umair Yasin; Muhammad Arif Ali (Journal of Plant Growth Regulation, 2021)

Genome-wide analysis of ARF transcription factors reveals HcARF5 expression profile associated with the biosynthesis of β-ocimene synthase in Hedychium coronarium - Farhat Abbas; Yanguo Ke; Yiwei Zhou; Yunyi Yu; Muhammad Waseem; Umair Ashraf; Xinyue Li; Rangcai Yu; Yanping Fan (Plant Cell Reports, 2021)

Plantations modified leaf elemental stoichiometry compared to the native shrub community in karst areas, Southwest of China - Jiahao Wen; Huimin Tao; Baoming Du; Dafeng Hui; Ningxiao Sun; Muhammad Umair; Chunjiang Liu (Trees, 2021)

Surging trends in prescriptions and costs of antidepressants in England amid COVID-19 - Shahad A. Rabeea; Hamid A. Merchant; Muhammad Umair Khan; Chia Siang Kow; Syed Shahzad Hasan (DARU Journal of Pharmaceutical Sciences, 2021)
The social restrictions amid coronavirus disease 2019 (COVID-19) pandemic have posed a serious threat to mental health and have implications in the use of medications for mental health including antidepressants (ADs). This study investigated the trends in prescriptions and costs of various ADs in England during COVID-19 pandemic. National prescribing rates and net ingredient costs (NIC) of all ADs prescriptions during 2016 to 2020 were analyed. The total number of ADs prescriptions dispensed during COVID-19 pandemic (January to December 2020) were 78 million, 4 million more than in 2019 that costed NHS England £ 139 million more than in 2019. Sertraline, an SSRI antidepressant drug, alone accounted for an extra £113 million during 2020 than in 2019. The peak dispensing for ADs was observed in March 2020 while the total costs for AD drugs peaked in April 2020. The rising prescription costs for ADs during COVID-19 pandemic is a potential cause of concern, in particular the increasing use in adolescents and younger adults needs attention, who are at a higher risk of life-threatening adverse drug reactions.

Causal analysis of the dynamic link between energy growth and environmental quality for agriculture sector: a piece of evidence from India - Snovia Naseem; Tong Guang Ji; Umair Kashif; Muhammad Zulqarnain Arshad (Environment, Development and Sustainability, 2021)

Heat stress in cultivated plants: nature, impact, mechanisms, and mitigation strategies—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Lorenzo Barbanti; Muhammad Aamer; Muhammad Mehmood Iqbal; Muhammad Nawaz; Athar Mahmood; Abid Ali; Muhammad Talha Aslam (Plant Biosystems, 2021)

Spatiotemporal analysis of crop water requirements in Lower Chenab Canal (LCC) Irrigation System for the better management of water resources - Muhammad Usman; Ejaz Hussain; Umair Rabbani; Shahid Ghazi; Syed M. Irteza; Shamaila Gull (Arabian Journal of Geosciences, 2021)

Transfer Learning for Prognostics and Health Management (PHM) of Marine Air Compressors - Magnus Gribbestad; Muhammad Umair Hassan; Ibrahim A. Hameed (Journal of Marine Science and Engineering, 2021)
Prognostics is an engineering discipline focused on predicting the time at which a system or a component will no longer perform its intended function. Due to the requirements of system safety and reliability, the correct diagnosis or prognosis of abnormal condition plays a vital role in the maintenance of industrial systems. It is expected that new requirements in regard to autonomous ships will push suppliers of maritime equipment to provide more insight into the conditions of their systems. One of the stated challenges with these systems is having enough run-to-failure examples to build accurate-enough prognostic models. Due to the scarcity of enough reliable data, transfer learning is established as a successful approach to improve and reduce the need to labelled examples. Transfer learning has shown excellent capabilities in image classification problems. Little work has been done to explore and exploit the use of transfer learning in prognostics. In this paper, various deep learning models are used to predict the remaining useful life (RUL) of air compressors. Here, transfer learning is applied by building a separate prognostics model trained on turbofan engines. It has been found that several of the explored transfer learning architectures were able to improve the predictions on air compressors. The research results suggest transfer learning as a promising research field towards more accurate and reliable prognostics.

N2O Emissions Mitigation in Acidic Soil Following Biochar Application Under Different Moisture Regimes - Muhammad Aamer; Muhammad Shaaban; Muhammad Umair Hassan; Liu Ying; Tang Haiying; Ma Qiaoying; Hassan Munir; Adnan Rasheed; Li Xinmei; Li Ping; Huang Guoqin (Journal of Soil Science and Plant Nutrition, 2020)

Comparative Response of Two Rice (Oryza sativa L.) Cultivars to Applied Zinc and Manganese for Mitigation of Salt Stress - Faisal Nadeem; Muhammad Azhar; Muhammad Anwar-ul-Haq; Muhammad Sabir; Tayyaba Samreen; Abdullah Tufail; Hafiz Umair Masood Awan; Wu Juan (Journal of Soil Science and Plant Nutrition, 2020)

Landslides assessment using geophysical and passive radon exhalation detection techniques in Murree Hills, northern Pakistan: Implication for environmental hazard assessment - Khawar Ashfaq Ahmed; Sarfraz Khan; Mahmood Sultan; Umair Bin Nisar; Muhammad Rizwan Mughal; Shahid Nadeem Qureshi (Journal of Earth System Science, 2020)

Characterization and adsorption capacity of modified 3D porous aerogel from grapefruit peels for removal of oils and organic solvents - Muhammad Imran; Ashraful Islam; Muhammad Umair Farooq; Junpei Ye; Panyue Zhang (Environmental Science and Pollution Research, 2020)

Enhanced uptake of Cd, Cr, and Cu in Catharanthus roseus (L.) G.Don by Bacillus cereus: application of moss and compost to reduce metal availability - Muhammad Umair Mushtaq; Ameena Iqbal; Ismat Nawaz; Cyrus Raza Mirza; Sohail Yousaf; Ghazanfar Farooq; Muhammad Arif Ali; Aqib Hassan Ali Khan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

Chemical fractionation and risk assessment of trace elements in sewage sludge generated from various states of Pakistan - Umair Riaz; Ghulam Murtaza; Saifullah; Muhammad Farooq; Humera Aziz; Ayesha Abdul Qadir; Shahzada Munawar Mehdi; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Gene expression of thrombomodulin, TNF-α and NF-KB in coronary artery disease patients of Pakistan - Muhammad Rafiq; Afrose Liaquat; Nadia Saeed; Ghassan Umair Shamshad; Sana Mumtaz; Muhammad Jawad Khan (Molecular Biology Reports, 2020)

Growth, Biomass Production, and Yield Potential of Quinoa (Chenopodium quinoa Willd.) as Affected by Planting Techniques Under Irrigated Conditions - Saif Ali; Muhammad Umer Chattha; Muhammad Umair Hassan; Imran Khan; Muhammad Bilal Chattha; Babar Iqbal; Muzammal Rehman; Muhammad Nawaz; Muhammad Zubair Amin (International Journal of Plant Production, 2020)

Geoinformatics and geophysical survey-based estimation of best groundwater potential sites through surface and subsurface indicators - Umair Rasool; Jianping Chen; Shafi Muhammad; Jamil Siddique; Senapathi Venkatramanan; Chidambaram Sabarathinam; Muhammad Amir Siddique; Muhammad Awais Rasool (Arabian Journal of Geosciences, 2020)

Citric acid enhanced phytoextraction of nickel (Ni) and alleviate Mentha piperita (L.) from Ni-induced physiological and biochemical damages - Kashaf Ul Khair; Mujahid Farid; Umair Ashraf; Muhammad Zubair; Muhammad Rizwan; Sheharyaar Farid; Hafiz Khuzama Ishaq; Usman Iftikhar; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

Influence of Pseudomonas japonica and organic amendments on the growth and metal tolerance of Celosia argentea L. - Ameena Iqbal; Muhammad Umair Mushtaq; Aqib Hassan Ali Khan; Ismat Nawaz; Sohail Yousaf; Zeshan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

Effects of Silicon and Phosphatic Fertilization on Rice Yield and Soil Fertility - Liying Wang; Umair Ashraf; Chunrong Chang; Muhammad Abrar; Xiong Cheng (Journal of Soil Science and Plant Nutrition, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Microzonation map of the Abbottabad basin and immediate surroundings - Sarfraz Khan; Muhammad Waseem; Muhammad Asif Khan; Zahid Hussain; Waqas Ahmed; Ahmad Hamad Khaliq; Nisar Bin Umair; Mian Luqman Hussain (Journal of Seismology, 2020)

Loop-mediated isothermal amplification for the detection of R81T mutation in nAChR with crude genomic DNA extracted from individual Myzus persicae - Muhammad Umair Sial; Zhenzhen Zhao; Lan Zhang; Yanning Zhang; Liangang Mao; Hongyun Jiang (Journal of Pest Science, 2020)

Genome Wide Identification and Expression Profiles of TALE Genes in Pineapple (Ananas comosus L) - Hina Ali; Yanhui Liu; Syed Muhammad Azam; Imran Ali; Umair Ali; Weimin Li; Hafiza Javaria Ashraf; Yang Jie; Stefan Olsson; Yuan Qin (Tropical Plant Biology, 2019)

The Effect of Encapsulation on The Stability of Probiotic Bacteria in Ice Cream and Simulated Gastrointestinal Conditions - Muhammad Afzaal; Farhan Saeed; Muhammad Umair Arshad; Muhammad Tahir Nadeem; Muhammad Saeed; Tabussam Tufail (Probiotics and Antimicrobial Proteins, 2019)

Karst rocky desertification does not erode ectomycorrhizal fungal species richness but alters microbial community structure - Nan Hui; Ningxiao Sun; Hongmei Du; Muhammad Umair; Hongzhang Kang; Xinxin Liu; Martin Romantschuk; Chunjiang Liu (Plant and Soil, 2019)

Ionic cross-linking of cellulose nanofibers: an approach to enhance mechanical stability for dynamic adsorption - Muhammad Muqeet; Umair Ahmed Qureshi; Rasool Bux Mahar; Zeeshan Khatri; Farooq Ahmed; Ick-Soo Kim (Environmental Science and Pollution Research, 2019)

Development and Evaluation of Optimized Thiolated Chitosan Proniosomal Gel Containing Duloxetine for Intranasal Delivery - Maryam khatoon; Muhammad Farhan Sohail; Gul Shahnaz; Fiza ur Rehman; Fakhar-ud-Din; Asim ur Rehman; Naseem Ullah; Umair Amin; Gul Majid Khan; Kifayat Ullah Shah (AAPS PharmSciTech, 2019)

Composted Sugarcane By-product Press Mud Cake Supports Wheat Growth and Improves Soil Properties - Muhammad Umer Chattha; Muhammad Umair Hassan; Lorenzo Barbanti; Muhammad Bilal Chattha; Imran Khan; Muhammad Usman; Abid Ali; Muhammad Nawaz (International Journal of Plant Production, 2019)

Identification and analysis of driving factors of CO2 emissions from economic growth in Pakistan - Zubair Akram; Jean Engo; Umair Akram; Muhammad Wasif Zafar (Environmental Science and Pollution Research, 2019)

Nickel toxicity in plants: reasons, toxic effects, tolerance mechanisms, and remediation possibilities—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Muhammad Aamer; Muhammad Nawaz; Abid Ali; Muhammad Aman Ullah Khan; Tahir Abbas Khan (Environmental Science and Pollution Research, 2019)

Ultrasonic seed treatment improved physiological and yield traits of rice under lead toxicity - Gangshun Rao; Umair Ashraf; Suihua Huang; Siren Cheng; Muhammad Abrar; Zhaowen Mo; Shenggang Pan; Xiangru Tang (Environmental Science and Pollution Research, 2018)

Strategic use of water: a step toward cadmium-free basmati rice (Oryza sativa L.) - Muhammad Naveed; Saifullah; Umair Riaz; Ghulam Murtaza; Sadia Bibi; Ammara Arooj; Qamar uz Zaman (Paddy and Water Environment, 2018)

Cucurmin, anticancer, & antitumor perspectives: A comprehensive review - Muhammad Imran; Azmat Ullah; Farhan Saeed; Muhammad Nadeem; Muhammad Umair Arshad; Hafiz Ansar Rasul Suleria (Critical Reviews in Food Science and Nutrition, 2018)

Performance of sorghum cultivars for biomass quality and biomethane yield grown in semi-arid area of Pakistan - Muhammad Umair Hassan; Muhammad Umer Chattha; Athar Mahmood; Shahbaz Talib Sahi (Environmental Science and Pollution Research, 2018)

Removal of lead from aqueous solution using polyacrylonitrile/magnetite nanofibers - Hammad Malik; Umair Ahmed Qureshi; Muhammad Muqeet; Rasool Bux Mahar; Farooq Ahmed; Zeeshan Khatri (Environmental Science and Pollution Research, 2018)

Ellis–van Creveld syndrome and profound deafness resulted by sequence variants in the EVC / EVC2 and TMC1 genes - Muhammad Umair; Heide Seidel; Ishtiaq Ahmed; Asmat Ullah; Tobias B. Haack; Bader Alhaddad; Abid Jan; Afzal Rafique; Tim M. Strom; Farooq Ahmad; Thomas Meitinger; Wasim Ahmad (Journal of Genetics, 2017)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Exogenous application of plant growth regulators (PGRs) induces chilling tolerance in short-duration hybrid maize - Muhammad Ahmed Waqas; Imran Khan; Muhammad Javaid Akhter; Mehmood Ali Noor; Umair Ashraf (Environmental Science and Pollution Research, 2017)

Aluminum and Chromium Toxicity in Maize: Implications for Agronomic Attributes, Net Photosynthesis, Physio-Biochemical Oscillations, and Metal Accumulation in Different Plant Parts - Shakeel Ahmad Anjum; Umair Ashraf; Imran Khan; Mohsin Tanveer; Muhammad Farrukh Saleem; Longchang Wang (Water, Air, & Soil Pollution, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

Sediment yield assessment and identification of check dam sites for Rawal Dam catchment - Nida Samad; Muhammad Hamid Chauhdry; Muhammad Ashraf; Muhammad Saleem; Qudsia Hamid; Umair Babar; Hassan Tariq; Muhammad Shahid Farid (Arabian Journal of Geosciences, 2016)

Stratigraphic and sedimentological attributes in Hazara Basin Lesser Himalaya, North Pakistan: their role in deciphering minerals potential - Muhammad Umar; Muhammad Amjad Sabir; Muhammad Farooq; Malik Muhammad Saud Sajid Khan; Faridullah Faridullah; Umair Khan Jadoon; Abdul Salam Khan (Arabian Journal of Geosciences, 2015)

Nutraceutical and Functional Scenario of Wheat Straw - Imran Pasha; Farhan Saeed; Khalid Waqas; Faqir Muhammad Anjum; Muhammad Umair Arshad (Critical Reviews in Food Science and Nutrition, 2013)

Some new prospects in the understanding of the molecular basis of the pathogenesis of stroke - Sheikh Arshad Saeed; Kaneez Fatima Shad; Taimur Saleem; Faisal Javed; Muhammad Umair Khan (Experimental Brain Research, 2007)